Maximum persistency via iterative relaxed inference with graphical models - Shekhovtsov, Alexander; Swoboda, Paul; Savchynskyy, Bogdan (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We consider the NP-hard problem of MAP-inference for undirected discrete graphical models. We propose a polynomial time and practically efficient algorithm for finding a part of its optimal solution. Specifically, our algorithm marks some labels of the considered graphical model either as (i) optimal, meaning that they belong to all optimal solutions of the inference problem; (ii) non-optimal if they provably do not belong to any solution. With access to an exact solver of a linear programming relaxation to the MAP-inference problem, our algorithm marks the maximal possible (in a specified sense) number of labels. We also present a version of the algorithm, which has access to a suboptimal dual solver only and still can ensure the (non-)optimality for the marked labels, although the overall number of the marked labels may decrease. We propose an efficient implementation, which runs in time comparable to a single run of a suboptimal dual solver. Our method is well-scalable and shows state-of-the-art results on computational benchmarks from machine learning and computer vision.

Sr2Pt8−xAs: A layered incommensurately modulated metal with saturated resistivity - Martino, Edoardo; Arakcheeva, Alla; Autès, Gabriel; Pisoni, Andrea; Bachmann, Maja D.; Modic, Kimberly A; Helm, Toni; Yazyev, Oleg V.; Moll, Philip J. W.; Forró, László; Katrych, Sergiy (IUCrJ)
The high-pressure synthesis and incommensurately modulated structure are reported for the new compound Sr2Pt8−xAs, with x = 0.715 (5). The structure consists of Sr2Pt3As layers alternating with Pt-only corrugated grids. Ab initio calculations predict a metallic character with a dominant role of the Pt d electrons. The electrical resistivity (ρ) and Seebeck coefficient confirm the metallic character, but surprisingly, ρ showed a near-flat temperature dependence. This observation fits the description of the Mooij correlation for electrical resistivity in disordered metals, originally developed for statistically distributed point defects. The discussed material has a long-range crystallographic order, but the high concentration of Pt vacancies, incommensurately ordered, strongly influences the electronic conduction properties. This result extends the range of validity of the Mooij correlation to long-range ordered incommensurately modulated vacancies. Motivated by the layered structure, the resistivity anisotropy was measured in a focused-ion-beam micro-fabricated well oriented single crystal. A low resistivity anisotropy indicates that the layers are electrically coupled and conduction channels along different directions are intermixed.

Quantum limit transport and destruction of the Weyl nodes in TaAs - Ramshaw, B. J.; Modic, Kimberly A; Shekhter, Arkady; Zhang, Yi; Kim, Eun-Ah; Moll, Philip J. W.; Bachmann, Maja D.; Chan, M. K.; Betts, J. B.; Balakirev, F.; Migliori, A.; Ghimire, N. J.; et al. (Nature Communications)
Weyl fermions are a recently discovered ingredient for correlated states of electronic matter. A key difficulty has been that real materials also contain non-Weyl quasiparticles, and disentangling the experimental signatures has proven challenging. Here we use magnetic fields up to 95 T to drive the Weyl semimetal TaAs far into its quantum limit, where only the purely chiral 0th Landau levels of the Weyl fermions are occupied. We find the electrical resistivity to be nearly independent of magnetic field up to 50 T: unusual for conventional metals but consistent with the chiral anomaly for Weyl fermions. Above 50 T we observe a two-order-of-magnitude increase in resistivity, indicating that a gap opens in the chiral Landau levels. Above 80 T we observe strong ultrasonic attenuation below 2 K, suggesting a mesoscopically textured state of matter. These results point the way to inducing new correlated states of matter in the quantum limit of Weyl semimetals.

Resonant torsion magnetometry in anisotropic quantum materials - Modic, Kimberly A; Bachmann, Maja D.; Ramshaw, B. J.; Arnold, F.; Shirer, K. R.; Estry, Amelia; Betts, J. B.; Ghimire, Nirmal J.; Bauer, E. D.; Schmidt, Marcus; Baenitz, Michael; Svanidze, E.; et al. (Nature Communications)
Unusual behavior in quantum materials commonly arises from their effective low-dimensional physics, reflecting the underlying anisotropy in the spin and charge degrees of freedom. Here we introduce the magnetotropic coefficient k = ∂2F/∂θ2, the second derivative of the free energy F with respect to the magnetic field orientation θ in the crystal. We show that the magnetotropic coefficient can be quantitatively determined from a shift in the resonant frequency of a commercially available atomic force microscopy cantilever under magnetic field. This detection method enables part per 100 million sensitivity and the ability to measure magnetic anisotropy in nanogram-scale samples, as demonstrated on the Weyl semimetal NbP. Measurement of the magnetotropic coefficient in the spin-liquid candidate RuCl3 highlights its sensitivity to anisotropic phase transitions and allows a quantitative comparison to other thermodynamic coefficients via the Ehrenfest relations.

Chiral spin order in some purported Kitaev spin-liquid compounds - Modic, Kimberly A; Ramshaw, B. J.; Shekhter, A.; Varma, C. M. (Physical Review B)
We examine recent magnetic torque measurements in two compounds, γ−Li2IrO3 and RuCl3, which have been discussed as possible realizations of the Kitaev model. The analysis of the reported discontinuity in torque, as an external magnetic field is rotated across the c axis in both crystals, suggests that they have a translationally invariant chiral spin order of the form ⟨Si⋅(Sj×Sk)⟩≠0 in the ground state and persisting over a very wide range of magnetic field and temperature. An extraordinary |B|B2 dependence of the torque for small fields, beside the usual B2 part, is predicted by the chiral spin order. Data for small fields are available for γ−Li2IrO3 and are found to be consistent with the prediction upon further analysis. Other experiments such as inelastic scattering and thermal Hall effect and several questions raised by the discovery of chiral spin order, including its topological consequences, are discussed.

Scale-invariant magnetoresistance in a cuprate superconductor - Giraldo-Gallo, P.; Galvis, J. A.; Stegen, Z.; Modic, Kimberly A; Balakirev, F. F.; Betts, J. B.; Lian, X.; Moir, C.; Riggs, S. C.; Wu, J.; Bollinger, A. T.; He, X.; et al. (Science)
The anomalous metallic state in the high-temperature superconducting cuprates is masked by superconductivity near a quantum critical point. Applying high magnetic fields to suppress superconductivity has enabled detailed studies of the normal state, yet the direct effect of strong magnetic fields on the metallic state is poorly understood. We report the high-field magnetoresistance of thin-film La2–xSrxCuO4 cuprate in the vicinity of the critical doping, 0.161 ≤ p ≤ 0.190. We find that the metallic state exposed by suppressing superconductivity is characterized by magnetoresistance that is linear in magnetic fields up to 80 tesla. The magnitude of the linear-in-field resistivity mirrors the magnitude and doping evolution of the well-known linear-in-temperature resistivity that has been associated with quantum criticality in high-temperature superconductors.

Synchronous multi-GPU training for deep learning with low-precision communications: An empirical study - Grubic, Demjan; Tam, Leo; Alistarh, Dan-Adrian; Zhang, Ce (Proceedings of the 21st International Conference on Extending Database Technology)
Training deep learning models has received tremendous research interest recently. In particular, there has been intensive research on reducing the communication cost of training when using multiple computational devices, through reducing the precision of the underlying data representation. Naturally, such methods induce system trade-offs—lowering communication precision could de-crease communication overheads and improve scalability; but, on the other hand, it can also reduce the accuracy of training. In this paper, we study this trade-off space, and ask:Can low-precision communication consistently improve the end-to-end performance of training modern neural networks, with no accuracy loss?From the performance point of view, the answer to this question may appear deceptively easy: compressing communication through low precision should help when the ratio between communication and computation is high. However, this answer is less straightforward when we try to generalize this principle across various neural network architectures (e.g., AlexNet vs. ResNet),number of GPUs (e.g., 2 vs. 8 GPUs), machine configurations(e.g., EC2 instances vs. NVIDIA DGX-1), communication primitives (e.g., MPI vs. NCCL), and even different GPU architectures(e.g., Kepler vs. Pascal). Currently, it is not clear how a realistic realization of all these factors maps to the speed up provided by low-precision communication. In this paper, we conduct an empirical study to answer this question and report the insights.

Minimum description length codes are critical - Cubero, Ryan J; Marsili, Matteo; Roudi, Yasser (Entropy)
In the Minimum Description Length (MDL) principle, learning from the data is equivalent to an optimal coding problem. We show that the codes that achieve optimal compression in MDL are critical in a very precise sense. First, when they are taken as generative models of samples, they generate samples with broad empirical distributions and with a high value of the relevance, defined as the entropy of the empirical frequencies. These results are derived for different statistical models (Dirichlet model, independent and pairwise dependent spin models, and restricted Boltzmann machines). Second, MDL codes sit precisely at a second order phase transition point where the symmetry between the sampled outcomes is spontaneously broken. The order parameter controlling the phase transition is the coding cost of the samples. The phase transition is a manifestation of the optimality of MDL codes, and it arises because codes that achieve a higher compression do not exist. These results suggest a clear interpretation of the widespread occurrence of statistical criticality as a characterization of samples which are maximally informative on the underlying generative process.
Keywords: Minimum Description Length; normalized maximum likelihood; statistical criticality; phase transitions; large deviations

Electrochemical oxidation of Lithium Carbonate generates singlet oxygen - Mahne, Nika; Renfrew, Sara E.; McCloskey, Bryan D.; Freunberger, Stefan Alexander (Angewandte Chemie International Edition)
Solid alkali metal carbonates are universal passivation layer components of intercalation battery materials and common side products in metal‐O2 batteries, and are believed to form and decompose reversibly in metal‐O2/CO2 cells. In these cathodes, Li2CO3 decomposes to CO2 when exposed to potentials above 3.8 V vs. Li/Li+. However, O2 evolution, as would be expected according to the decomposition reaction 2 Li2CO3→4 Li++4 e−+2 CO2+O2, is not detected. O atoms are thus unaccounted for, which was previously ascribed to unidentified parasitic reactions. Here, we show that highly reactive singlet oxygen (1O2) forms upon oxidizing Li2CO3 in an aprotic electrolyte and therefore does not evolve as O2. These results have substantial implications for the long‐term cyclability of batteries: they underpin the importance of avoiding 1O2 in metal‐O2 batteries, question the possibility of a reversible metal‐O2/CO2 battery based on a carbonate discharge product, and help explain the interfacial reactivity of transition‐metal cathodes with residual Li2CO3.

Quasi-monodisperse transition-metal-doped BaTiO3 (M = Cr, Mn, Fe, Co) colloidal nanocrystals with multiferroic properties - Costanzo, Tommaso; McCracken, John; Rotaru, Aurelian; Caruntu, Gabriel (ACS Applied Nano Materials)
The recent demand of multifunctional materials and devices for advanced applications in energy conversion and data storage resulted into a revival of multiferroics, that is, materials characterized by the coexistence of ferromagnetism and ferroelectricity. Despite intense efforts made in the past decade, single-phase room temperature multiferroics are yet to be discovered/fabricated. Nanostructured ferroic materials could potentially exhibit multiferroism since a high fraction of their atoms/ions are superficial, thereby altering significantly the properties of the bulk phase. Alternately, a magnetic order can be induced into ferroelectric materials upon aliovalent doping with magnetic ions. Here, we report on the synthesis of aggregate-free single-phase transition-metal-doped BaTiO3 quasi-monodisperse cuboidal nanocrystals (NC) which exhibit multiferroic properties at room temperature and can be suitable for applications in data storage. The proposed synthetic route allows the inclusion of a high concentration of magnetic ions such as Mn+ (M = Cr, Mn, Fe, Co) up to a nominal concentration of 4% without the formation of any secondary phase. The size of the nanocrystals was controlled in a wide range from ∼15 up to ∼70 nm by varying the reaction time from 48 to 144 h. The presence of unpaired electrons and their magnetic ordering have been probed by electron paramagnetic resonance spectroscopy (EPR), and a vibrating sample magnetometer (VSM). Likewise, an acentric structure, associated with the existence of a dielectric polarization, was observed by lattice dynamics analysis and piezoresponse force microscopy (PFM). These results show that high-quality titanium-containing perovskite nanocrystals which display multiferroic properties at room temperature can be fabricated via soft solution-based synthetic routes, and the properties of these materials can be modulated by changing the size of the nanocrystals and the concentration of the dopant thereby opening the door to the design and study of single-phase multiferroic materials.

Quantifying total superoxide, peroxide, and carbonaceous compounds in metal–O2 batteries and the solid electrolyte interphase - Schafzahl, Bettina; Mourad, Eléonore; Schafzahl, Lukas; Petit, Yann K.; Raju, Anjana R.; Thotiyl, Musthafa Ottakam; Wilkening, Martin; Slugovc, Christian; Freunberger, Stefan Alexander (ACS Energy Letters)
Passivation layers on electrode materials are ubiquitous in nonaqueous battery chemistries and strongly govern performance and lifetime. They comprise breakdown products of the electrolyte including carbonate, alkyl carbonates, alkoxides, carboxylates, and polymers. Parasitic chemistry in metal–O2 batteries forms similar products and is tied to the deviation of the O2 balance from the ideal stoichiometry during formation/decomposition of alkaline peroxides or superoxides. Accurate and integral quantification of carbonaceous species and peroxides or superoxides in battery electrodes remains, however, elusive. We present a refined procedure to quantify them accurately and sensitively by pointing out and rectifying pitfalls of previous procedures. Carbonaceous compounds are differentiated into inorganic and organic ones. We combine mass and UV–vis spectrometry to quantify evolved O2 and complexed peroxide and CO2 evolved from carbonaceous compounds by acid treatment and Fenton’s reaction. The capabilities of the method are exemplified by means of Li–O2 and Na–O2 cathodes, graphite anodes, and LiNi0.8Co0.15Al0.05O2 cathodes.

Inter-backbone charge transfer as prerequisite for long-range conductivity in perylene bisimide hydrogels - Burian, Max; Rigodanza, Francesco; Demitri, Nicola; D̵ord̵ević, Luka; Marchesan, Silvia; Steinhartova, Tereza; Letofsky-Papst, Ilse; Khalakhan, Ivan; Mourad, Eléonore; Freunberger, Stefan Alexander; Amenitsch, Heinz; Prato, Maurizio; et al. (ACS Nano)
Hydrogelation, the self-assembly of molecules into soft, water-loaded networks, is one way to bridge the structural gap between single molecules and functional materials. The potential of hydrogels, such as those based on perylene bisimides, lies in their chemical, physical, optical, and electronic properties, which are governed by the supramolecular structure of the gel. However, the structural motifs and their precise role for long-range conductivity are yet to be explored. Here, we present a comprehensive structural picture of a perylene bisimide hydrogel, suggesting that its long-range conductivity is limited by charge transfer between electronic backbones. We reveal nanocrystalline ribbon-like structures as the electronic and structural backbone units between which charge transfer is mediated by polar solvent bridges. We exemplify this effect with sensing, where exposure to polar vapor enhances conductivity by 5 orders of magnitude, emphasizing the crucial role of the interplay between structural motif and surrounding medium for the rational design of devices based on nanocrystalline hydrogels.

Long-chain Li and Na alkyl carbonates as solid electrolyte interphase components: Structure, ion transport, and mechanical properties - Schafzahl, Lukas; Ehmann, Heike; Kriechbaum, Manfred; Sattelkow, Jürgen; Ganner, Thomas; Plank, Harald; Wilkening, Martin; Freunberger, Stefan Alexander (Chemistry of Materials)
The solid electrolyte interphase (SEI) in Li and Na ion batteries forms when highly reducing or oxidizing electrode materials come into contact with a liquid organic electrolyte. Its ability to form a mechanically robust, ion-conducting, and electron-insulating layer critically determines performance, cycle life, and safety. Li or Na alkyl carbonates (LiAC and NaAC, respectively) are lead SEI components in state-of-the-art carbonate based electrolytes, and our fundamental understanding of their charge transport and mechanical properties may hold the key to designing electrolytes forming an improved SEI. We synthesized a homologous series of LiACs and NaACs from methyl to octyl analogues and characterized them with respect to structure, ionic conductivity, and stiffness. The compounds assume layered structures except for the lithium methyl carbonate. Room-temperature conductivities were found to be ∼10–9 S cm–1 for lithium methyl carbonate, <10–12 S cm–1 for the other LiACs, and <10–12 S cm–1 for the NaACs with ion transport mostly attributed to grain boundaries. While LiACs show stiffnesses of ∼1 GPa, NaACs become significantly softer with increasing chain lengths. These findings will help to more precisely interpret the complex results from charge transport and mechanical characterization of real SEIs and can give a rationale for influencing the SEI’s mechanical properties via the electrolyte.

Proofs of catalytic space - Pietrzak, Krzysztof Z (10th Innovations in Theoretical Computer Science Conference (ITCS 2019))
Proofs of space (PoS) [Dziembowski et al., CRYPTO'15] are proof systems where a prover can convince a verifier that he "wastes" disk space. PoS were introduced as a more ecological and economical replacement for proofs of work which are currently used to secure blockchains like Bitcoin. In this work we investigate extensions of PoS which allow the prover to embed useful data into the dedicated space, which later can be recovered. Our first contribution is a security proof for the original PoS from CRYPTO'15 in the random oracle model (the original proof only applied to a restricted class of adversaries which can store a subset of the data an honest prover would store). When this PoS is instantiated with recent constructions of maximally depth robust graphs, our proof implies basically optimal security. As a second contribution we show three different extensions of this PoS where useful data can be embedded into the space required by the prover. Our security proof for the PoS extends (non-trivially) to these constructions. We discuss how some of these variants can be used as proofs of catalytic space (PoCS), a notion we put forward in this work, and which basically is a PoS where most of the space required by the prover can be used to backup useful data. Finally we discuss how one of the extensions is a candidate construction for a proof of replication (PoR), a proof system recently suggested in the Filecoin whitepaper.

Tutorial: Product properties in multiferroic nanocomposites - Viehland, Dwight; Li, Jie Fang; Yang, Yaodong; Costanzo, Tommaso; Yourdkhani, Amin; Caruntu, Gabriel; Zhou, Peng; Zhang, Tianjin; Li, Tianqian; Gupta, Arunava; Popov, Maksym; Srinivasan, Gopalan (Journal of Applied Physics)
The coupling between magnetic and electric subsystems in composites of ferromagnetic and ferroelectric phases is a product property that is facilitated by mechanical strain that arises due to magnetostriction and the piezoelectric effect in the constituent phases. Such multiferroic composites are of immense interests for studies on the physics of electromagnetic coupling and for use in a variety of applications. Here, we focus on magneto-electric (ME) coupling in nanocomposites. Particular emphasis is on core-shell particles and coaxial fibers, thin film heterostructures, and planar structures with a variety of mechanical connectivity. A brief review of models that predict strong ME effects in nanostructures is followed by synthesis and characterization. Core-shell particulate composites can be prepared by hydrothermal processes and chemical or deoxyribonucleic acid-assisted assembly. Electrospinning techniques have been utilized to prepare defect free core-shell nanofibers. Core-shell particles and fibers can be assembled into superstructures with the aid of magnetic and electric fields and characterized for possible use in advanced technologies. Chemical-vapor deposition techniques have been shown to be effective for the preparation of heterostructures of ferrites and ferroelectrics. Exotic planar multiferroic structures with potential for enhancing ME coupling strengths are also considered. Scanning probe microscopy techniques are ideal for probing the nature of direct- and converse-ME coupling in individual nanostructures. Magnetoelectric characterization of assemblies of nanocomposites can be done by ME voltage coefficient, magnetic field induced polarization, and magneto-dielectric effects. We conclude with a brief discussion on possible avenues for strengthening the product properties in the nanocomposites.

Genotype effects contribute to variation in longitudinal methylome patterns in older people - Zhang, Qian; Marioni, Riccardo E; Robinson, Matthew Richard; Higham, Jon; Sproul, Duncan; Wray, Naomi R; Deary, Ian J; McRae, Allan F; Visscher, Peter M (Genome Medicine)
Background: DNA methylation levels change along with age, but few studies have examined the variation in the rate of such changes between individuals. Methods: We performed a longitudinal analysis to quantify the variation in the rate of change of DNA methylation between individuals using whole blood DNA methylation array profiles collected at 2–4 time points (N = 2894) in 954 individuals (67–90 years). Results: After stringent quality control, we identified 1507 DNA methylation CpG sites (rsCpGs) with statistically significant variation in the rate of change (random slope) of DNA methylation among individuals in a mixed linear model analysis. Genes in the vicinity of these rsCpGs were found to be enriched in Homeobox transcription factors and the Wnt signalling pathway, both of which are related to ageing processes. Furthermore, we investigated the SNP effect on the random slope. We found that 4 out of 1507 rsCpGs had one significant (P < 5 × 10−8/1507) SNP effect and 343 rsCpGs had at least one SNP effect (436 SNP-probe pairs) reaching genome-wide significance (P < 5 × 10−8). Ninety-five percent of the significant (P < 5 × 10−8) SNPs are on different chromosomes from their corresponding probes. Conclusions: We identified CpG sites that have variability in the rate of change of DNA methylation between individuals, and our results suggest a genetic basis of this variation. Genes around these CpG sites have been reported to be involved in the ageing process.

Evolutionary history and adaptation of a human pygmy population of Flores Island, Indonesia - Tucci, Serena; Vohr, Samuel H.; McCoy, Rajiv C.; Vernot, Benjamin; Robinson, Matthew Richard; Barbieri, Chiara; Nelson, Brad J.; Fu, Wenqing; Purnomo, Gludhug A.; Sudoyo, Herawati; Eichler, Evan E.; Barbujani, Guido; et al. (Science)
Flores Island, Indonesia, was inhabited by the small-bodied hominin species Homo floresiensis, which has an unknown evolutionary relationship to modern humans. This island is also home to an extant human pygmy population. Here we describe genome-scale single-nucleotide polymorphism data and whole-genome sequences from a contemporary human pygmy population living on Flores near the cave where H. floresiensis was found. The genomes of Flores pygmies reveal a complex history of admixture with Denisovans and Neanderthals but no evidence for gene flow with other archaic hominins. Modern individuals bear the signatures of recent positive selection encompassing the FADS (fatty acid desaturase) gene cluster, likely related to diet, and polygenic selection acting on standing variation that contributed to their short-stature phenotype. Thus, multiple independent instances of hominin insular dwarfism occurred on Flores.

Dissection of genetic variation and evidence for pleiotropy in male pattern baldness - Yap, Chloe X.; Sidorenko, Julia; Wu, Yang; Kemper, Kathryn E.; Yang, Jian; Wray, Naomi R.; Robinson, Matthew Richard; Visscher, Peter M. (Nature Communications)
Male pattern baldness (MPB) is a sex-limited, age-related, complex trait. We study MPB genetics in 205,327 European males from the UK Biobank. Here we show that MPB is strongly heritable and polygenic, with pedigree-heritability of 0.62 (SE = 0.03) estimated from close relatives, and SNP-heritability of 0.39 (SE = 0.01) from conventionally-unrelated males. We detect 624 near-independent genome-wide loci, contributing SNP-heritability of 0.25 (SE = 0.01), of which 26 X-chromosome loci explain 11.6%. Autosomal genetic variance is enriched for common variants and regions of lower linkage disequilibrium. We identify plausible genetic correlations between MPB and multiple sex-limited markers of earlier puberty, increased bone mineral density (rg = 0.15) and pancreatic β-cell function (rg = 0.12). Correlations with reproductive traits imply an effect on fitness, consistent with an estimated linear selection gradient of -0.018 per MPB standard deviation. Overall, we provide genetic insights into MPB: a phenotype of interest in its own right, with value as a model sex-limited, complex trait.

Improving genetic prediction by leveraging genetic correlations among human diseases and traits - Maier, Robert M.; Zhu, Zhihong; Lee, Sang Hong; Trzaskowski, Maciej; Ruderfer, Douglas M.; Stahl, Eli A.; Ripke, Stephan; Wray, Naomi R.; Yang, Jian; Visscher, Peter M.; Robinson, Matthew Richard (Nature Communications)
Genomic prediction has the potential to contribute to precision medicine. However, to date, the utility of such predictors is limited due to low accuracy for most traits. Here theory and simulation study are used to demonstrate that widespread pleiotropy among phenotypes can be utilised to improve genomic risk prediction. We show how a genetic predictor can be created as a weighted index that combines published genome-wide association study (GWAS) summary statistics across many different traits. We apply this framework to predict risk of schizophrenia and bipolar disorder in the Psychiatric Genomics consortium data, finding substantial heterogeneity in prediction accuracy increases across cohorts. For six additional phenotypes in the UK Biobank data, we find increases in prediction accuracy ranging from 0.7% for height to 47% for type 2 diabetes, when using a multi-trait predictor that combines published summary statistics from multiple traits, as compared to a predictor based only on one trait.

Imprint of assortative mating on the human genome - Yengo, Loic; Robinson, Matthew Richard; Keller, Matthew C.; Kemper, Kathryn E.; Yang, Yuanhao; Trzaskowski, Maciej; Gratten, Jacob; Turley, Patrick; Cesarini, David; Benjamin, Daniel J.; Wray, Naomi R.; Goddard, Michael E.; et al. (Nature Human Behaviour)
Preference for mates with similar phenotypes; that is, assortative mating, is widely observed in humans1,2,3,4,5 and has evolutionary consequences6,7,8. Under Fisher's classical theory6, assortative mating is predicted to induce a signature in the genome at trait-associated loci that can be detected and quantified. Here, we develop and apply a method to quantify assortative mating on a specific trait by estimating the correlation (θ) between genetic predictors of the trait from single nucleotide polymorphisms on odd- versus even-numbered chromosomes. We show by theory and simulation that the effect of assortative mating can be quantified in the presence of population stratification. We applied this approach to 32 complex traits and diseases using single nucleotide polymorphism data from ~400,000 unrelated individuals of European ancestry. We found significant evidence of assortative mating for height (θ = 3.2%) and educational attainment (θ = 2.7%), both of which were consistent with theoretical predictions. Overall, our results imply that assortative mating involves multiple traits and affects the genomic architecture of loci that are associated with these traits, and that the consequence of mate choice can be detected from a random sample of genomes.

Causal associations between risk factors and common diseases inferred from GWAS summary data - Zhu, Zhihong; Zheng, Zhili; Zhang, Futao; Wu, Yang; Trzaskowski, Maciej; Maier, Robert; Robinson, Matthew Richard; McGrath, John J.; Visscher, Peter M.; Wray, Naomi R.; Yang, Jian (Nature Communications)
Health risk factors such as body mass index (BMI) and serum cholesterol are associated with many common diseases. It often remains unclear whether the risk factors are cause or consequence of disease, or whether the associations are the result of confounding. We develop and apply a method (called GSMR) that performs a multi-SNP Mendelian randomization analysis using summary-level data from genome-wide association studies to test the causal associations of BMI, waist-to-hip ratio, serum cholesterols, blood pressures, height, and years of schooling (EduYears) with common diseases (sample sizes of up to 405,072). We identify a number of causal associations including a protective effect of LDL-cholesterol against type-2 diabetes (T2D) that might explain the side effects of statins on T2D, a protective effect of EduYears against Alzheimer’s disease, and bidirectional associations with opposite effects (e.g., higher BMI increases the risk of T2D but the effect of T2D on BMI is negative).

Global genetic differentiation of complex traits shaped by natural selection in humans - Guo, Jing; Wu, Yang; Zhu, Zhihong; Zheng, Zhili; Trzaskowski, Maciej; Zeng, Jian; Robinson, Matthew Richard; Visscher, Peter M.; Yang, Jian (Nature Communications)
There are mean differences in complex traits among global human populations. We hypothesize that part of the phenotypic differentiation is due to natural selection. To address this hypothesis, we assess the differentiation in allele frequencies of trait-associated SNPs among African, Eastern Asian, and European populations for ten complex traits using data of large sample size (up to ~405,000). We show that SNPs associated with height (P=2.46×10−5), waist-to-hip ratio (P=2.77×10−4), and schizophrenia (P=3.96×10−5) are significantly more differentiated among populations than matched “control” SNPs, suggesting that these trait-associated SNPs have undergone natural selection. We further find that SNPs associated with height (P=2.01×10−6) and schizophrenia (P=5.16×10−18) show significantly higher variance in linkage disequilibrium (LD) scores across populations than control SNPs. Our results support the hypothesis that natural selection has shaped the genetic differentiation of complex traits, such as height and schizophrenia, among worldwide populations.

Embracing polygenicity: A review of methods and tools for psychiatric genetics research - Maier, R. M.; Visscher, P. M.; Robinson, Matthew Richard; Wray, N. R. (Psychological Medicine)
The availability of genome-wide genetic data on hundreds of thousands of people has led to an equally rapid growth in methodologies available to analyse these data. While the motivation for undertaking genome-wide association studies (GWAS) is identification of genetic markers associated with complex traits, once generated these data can be used for many other analyses. GWAS have demonstrated that complex traits exhibit a highly polygenic genetic architecture, often with shared genetic risk factors across traits. New methods to analyse data from GWAS are increasingly being used to address a diverse set of questions about the aetiology of complex traits and diseases, including psychiatric disorders. Here, we give an overview of some of these methods and present examples of how they have contributed to our understanding of psychiatric disorders. We consider: (i) estimation of the extent of genetic influence on traits, (ii) uncovering of shared genetic control between traits, (iii) predictions of genetic risk for individuals, (iv) uncovering of causal relationships between traits, (v) identifying causal single-nucleotide polymorphisms and genes or (vi) the detection of genetic heterogeneity. This classification helps organise the large number of recently developed methods, although some could be placed in more than one category. While some methods require GWAS data on individual people, others simply use GWAS summary statistics data, allowing novel well-powered analyses to be conducted at a low computational burden.

Transformation of summary statistics from linear mixed model association on all-or-none traits to odds ratio - Lloyd-Jones, Luke R.; Robinson, Matthew Richard; Yang, Jian; Visscher, Peter M. (Genetics)
Genome-wide association studies (GWAS) have identified thousands of loci that are robustly associated with complex diseases. The use of linear mixed model (LMM) methodology for GWAS is becoming more prevalent due to its ability to control for population structure and cryptic relatedness and to increase power. The odds ratio (OR) is a common measure of the association of a disease with an exposure (e.g., a genetic variant) and is readably available from logistic regression. However, when the LMM is applied to all-or-none traits it provides estimates of genetic effects on the observed 0–1 scale, a different scale to that in logistic regression. This limits the comparability of results across studies, for example in a meta-analysis, and makes the interpretation of the magnitude of an effect from an LMM GWAS difficult. In this study, we derived transformations from the genetic effects estimated under the LMM to the OR that only rely on summary statistics. To test the proposed transformations, we used real genotypes from two large, publicly available data sets to simulate all-or-none phenotypes for a set of scenarios that differ in underlying model, disease prevalence, and heritability. Furthermore, we applied these transformations to GWAS summary statistics for type 2 diabetes generated from 108,042 individuals in the UK Biobank. In both simulation and real-data application, we observed very high concordance between the transformed OR from the LMM and either the simulated truth or estimates from logistic regression. The transformations derived and validated in this study improve the comparability of results from prospective and already performed LMM GWAS on complex diseases by providing a reliable transformation to a common comparative scale for the genetic effects.

Signatures of negative selection in the genetic architecture of human complex traits - Zeng, Jian; de Vlaming, Ronald; Wu, Yang; Robinson, Matthew Richard; Lloyd-Jones, Luke R.; Yengo, Loic; Yap, Chloe X.; Xue, Angli; Sidorenko, Julia; McRae, Allan F.; Powell, Joseph E.; Montgomery, Grant W.; et al. (Nature Genetics)
We develop a Bayesian mixed linear model that simultaneously estimates single-nucleotide polymorphism (SNP)-based heritability, polygenicity (proportion of SNPs with nonzero effects), and the relationship between SNP effect size and minor allele frequency for complex traits in conventionally unrelated individuals using genome-wide SNP data. We apply the method to 28 complex traits in the UK Biobank data (N = 126,752) and show that on average, 6% of SNPs have nonzero effects, which in total explain 22% of phenotypic variance. We detect significant (P < 0.05/28) signatures of natural selection in the genetic architecture of 23 traits, including reproductive, cardiovascular, and anthropometric traits, as well as educational attainment. The significant estimates of the relationship between effect size and minor allele frequency in complex traits are consistent with a model of negative (or purifying) selection, as confirmed by forward simulation. We conclude that negative selection acts pervasively on the genetic variants associated with human complex traits.

Evidence of directional and stabilizing selection in contemporary humans - Sanjak, Jaleal S.; Sidorenko, Julia; Robinson, Matthew Richard; Thornton, Kevin R.; Visscher, Peter M. (Proceedings of the National Academy of Sciences)
Modern molecular genetic datasets, primarily collected to study the biology of human health and disease, can be used to directly measure the action of natural selection and reveal important features of contemporary human evolution. Here we leverage the UK Biobank data to test for the presence of linear and nonlinear natural selection in a contemporary population of the United Kingdom. We obtain phenotypic and genetic evidence consistent with the action of linear/directional selection. Phenotypic evidence suggests that stabilizing selection, which acts to reduce variance in the population without necessarily modifying the population mean, is widespread and relatively weak in comparison with estimates from other species.

Enhanced diffusion by binding to the crosslinks of a polymer gel - Goodrich, Carl Peter; Brenner, Michael P.; Ribbeck, Katharina (Nature Communications)
Creating a selective gel that filters particles based on their interactions is a major goal of nanotechnology, with far-reaching implications from drug delivery to controlling assembly pathways. However, this is particularly difficult when the particles are larger than the gel’s characteristic mesh size because such particles cannot passively pass through the gel. Thus, filtering requires the interacting particles to transiently reorganize the gel’s internal structure. While significant advances, e.g., in DNA engineering, have enabled the design of nano-materials with programmable interactions, it is not clear what physical principles such a designer gel could exploit to achieve selective permeability. We present an equilibrium mechanism where crosslink binding dynamics are affected by interacting particles such that particle diffusion is enhanced. In addition to revealing specific design rules for manufacturing selective gels, our results have the potential to explain the origin of selective permeability in certain biological materials, including the nuclear pore complex.

Extensive mitochondrial population structure and haplotype-specific phenotypic variation in the Drosophila Genetic Reference Panel - Bevers, Roel P.J.; Litovchenko, Maria; Kapopoulou, Adamandia; Braman, Virginie S.; Robinson, Matthew Richard; Auwerx, Johan; Hollis, Brian; Deplancke, Bart (bioRxiv)
The Drosophila Genetic Reference Panel (DGRP) serves as a valuable resource to better understand the genetic landscapes underlying quantitative traits. However, such DGRP studies have so far only focused on nuclear genetic variants. To address this, we sequenced the mitochondrial genomes of >170 DGRP lines, identifying 229 variants including 21 indels and 7 frameshifts. We used our mitochondrial variation data to identify 12 genetically distinct mitochondrial haplotypes, thus revealing important population structure at the mitochondrial level. We further examined whether this population structure was reflected on the nuclear genome by screening for the presence of potential mito-nuclear genetic incompatibilities in the form of significant genotype ratio distortions (GRDs) between mitochondrial and nuclear variants. In total, we detected a remarkable 1,845 mito-nuclear GRDs, with the highest enrichment observed in a 40 kb region around the gene Sex-lethal (Sxl). Intriguingly, downstream phenotypic analyses did not uncover major fitness effects associated with these GRDs, suggesting that a large number of mito-nuclear GRDs may reflect population structure at the mitochondrial level rather than actual genomic incompatibilities. This is further supported by the GRD landscape showing particular large genomic regions associated with a single mitochondrial haplotype. Next, we explored the functional relevance of the detected mitochondrial haplotypes through an association analysis on a set of 259 assembled, non-correlating DGRP phenotypes. We found multiple significant associations with stress- and metabolism-related phenotypes, including food intake in males. We validated the latter observation by reciprocal swapping of mitochondrial genomes from high food intake DGRP lines to low food intake ones. In conclusion, our study uncovered important mitochondrial population structure and haplotype-specific metabolic variation in the DGRP, thus demonstrating the significance of incorporating mitochondrial haplotypes in geno-phenotype relationship studies.

ThreadScan: Automatic and scalable memory reclamation - Alistarh, Dan-Adrian; Leiserson, William; Matveev, Alexander; Shavit, Nir (ACM Transactions on Parallel Computing)
The concurrent memory reclamation problem is that of devising a way for a deallocating thread to verify that no other concurrent threads hold references to a memory block being deallocated. To date, in the absence of automatic garbage collection, there is no satisfactory solution to this problem; existing tracking methods like hazard pointers, reference counters, or epoch-based techniques like RCU are either prohibitively expensive or require significant programming expertise to the extent that implementing them efficiently can be worthy of a publication. None of the existing techniques are automatic or even semi-automated. In this article, we take a new approach to concurrent memory reclamation. Instead of manually tracking access to memory locations as done in techniques like hazard pointers, or restricting shared accesses to specific epoch boundaries as in RCU, our algorithm, called ThreadScan, leverages operating system signaling to automatically detect which memory locations are being accessed by concurrent threads. Initial empirical evidence shows that ThreadScan scales surprisingly well and requires negligible programming effort beyond the standard use of Malloc and Free.

Model compression via distillation and quantization - Polino, Antonio; Pascanu, Razvan; Alistarh, Dan-Adrian (6th International Conference on Learning Representations)
Deep neural networks (DNNs) continue to make significant advances, solving tasks from image classification to translation or reinforcement learning. One aspect of the field receiving considerable attention is efficiently executing deep models in resource-constrained environments, such as mobile or embedded devices. This paper focuses on this problem, and proposes two new compression methods, which jointly leverage weight quantization and distillation of larger teacher networks into smaller student networks. The first method we propose is called quantized distillation and leverages distillation during the training process, by incorporating distillation loss, expressed with respect to the teacher, into the training of a student network whose weights are quantized to a limited set of levels. The second method, differentiable quantization, optimizes the location of quantization points through stochastic gradient descent, to better fit the behavior of the teacher model. We validate both methods through experiments on convolutional and recurrent architectures. We show that quantized shallow students can reach similar accuracy levels to full-precision teacher models, while providing order of magnitude compression, and inference speedup that is linear in the depth reduction. In sum, our results enable DNNs for resource-constrained environments to leverage architecture and accuracy advances developed on more powerful devices.

Elektrochemische Oxidation von Lithiumcarbonat generiert Singulett-Sauerstoff - Mahne, Nika; Renfrew, Sara E.; McCloskey, Bryan D.; Freunberger, Stefan Alexander (Angewandte Chemie)
Feste Alkalicarbonate sind universelle Bestandteile von Passivierungsschichten an Materialien für Interkalationsbatterien, übliche Nebenprodukte in Metall‐O2‐Batterien, und es wird angenommen, dass sie sich reversibel in Metall‐O2 /CO2‐Zellen bilden und zersetzen. In all diesen Kathoden zersetzt sich Li2CO3 zu CO2, sobald es Spannungen >3.8 V vs. Li/Li+ ausgesetzt wird. Beachtenswert ist, dass keine O2‐Entwicklung detektiert wird, wie gemäß der Zersetzungsreaktion 2 Li2CO3 → 4 Li+ + 4 e− + 2 CO2 + O2 zu erwarten wäre. Deswegen war der Verbleib eines der O‐Atome ungeklärt und wurde nicht identifizierten parasitären Reaktionen zugerechnet. Hier zeigen wir, dass hochreaktiver Singulett‐Sauerstoff (1O2) bei der Oxidation von Li2CO3 in einem aprotischen Elektrolyten gebildet und daher nicht als O2 freigesetzt wird. Diese Ergebnisse haben weitreichende Auswirkungen auf die langfristige Zyklisierbarkeit von Batterien: sie untermauern die Wichtigkeit, 1O2 in Metall‐O2‐Batterien zu verhindern, stellen die Möglichkeit einer reversiblen Metall‐O2 /CO2‐Batterie basierend auf einem Carbonat‐Entladeprodukt in Frage und helfen, Grenzflächenreaktivität von Übergangsmetallkathoden mit Li2CO3‐Resten zu erklären.

Cortical signal propagation: Balance, amplify, transmit - Stroud, Jake P.; Vogels, Tim P (Neuron)
The neural code of cortical processing remains uncracked; however, it must necessarily rely on faithful signal propagation between cortical areas. In this issue of Neuron, Joglekar et al. (2018) show that strong inter-areal excitation balanced by local inhibition can enable reliable signal propagation in data-constrained network models of macaque cortex.

Motor primitives in space and time via targeted gain modulation in cortical networks - Stroud, Jake P.; Porter, Mason A.; Hennequin, Guillaume; Vogels, Tim P (Nature Neuroscience)
Motor cortex (M1) exhibits a rich repertoire of neuronal activities to support the generation of complex movements. Although recent neuronal-network models capture many qualitative aspects of M1 dynamics, they can generate only a few distinct movements. Additionally, it is unclear how M1 efficiently controls movements over a wide range of shapes and speeds. We demonstrate that modulation of neuronal input–output gains in recurrent neuronal-network models with a fixed architecture can dramatically reorganize neuronal activity and thus downstream muscle outputs. Consistent with the observation of diffuse neuromodulatory projections to M1, a relatively small number of modulatory control units provide sufficient flexibility to adjust high-dimensional network activity using a simple reward-based learning rule. Furthermore, it is possible to assemble novel movements from previously learned primitives, and one can separately change movement speed while preserving movement shape. Our results provide a new perspective on the role of modulatory systems in controlling recurrent cortical activity.

AllergoOncology: Generating a canine anticancer IgE against the epidermal growth factor receptor - Fazekas-Singer, Judit; Singer, Josef; Ilieva, Kristina M.; Matz, Miroslawa; Herrmann, Ina; Spillner, Edzard; Karagiannis, Sophia N.; Jensen-Jarolim, Erika (Journal of Allergy and Clinical Immunology)

Preclinical in vitro and in vivo evaluation of [18F]FE@SUPPY for cancer PET imaging: Limitations of a xenograft model for colorectal cancer - Balber, T.; Singer, Judit; Berroterán-Infante, N.; Dumanic, M.; Fetty, L.; Fazekas-Singer, J.; Vraka, C.; Nics, L.; Bergmann, M.; Pallitsch, K.; Spreitzer, H.; Wadsak, W.; et al. (Contrast Media & Molecular Imaging)
Molecular imaging probes such as PET-tracers have the potential to improve the accuracy of tumor characterization by directly visualizing the biochemical situation. Thus, molecular changes can be detected early before morphological manifestation. The A3 adenosine receptor (A3AR) is described to be highly expressed in colon cancer cell lines and human colorectal cancer (CRC), suggesting this receptor as a tumor marker. The aim of this preclinical study was the evaluation of FE@SUPPY as a PET-tracer for CRC using in vitro imaging and in vivo PET imaging. First, affinity and selectivity of FE@SUPPY and its metabolites were determined, proving the favorable binding profile of FE@SUPPY. The human adenocarcinoma cell line HT-29 was characterized regarding its hA3AR expression and was subsequently chosen as tumor graft. Promising results regarding the potential of FE@SUPPY as a PET-tracer for CRC imaging were obtained by autoradiography as ≥2.3-fold higher accumulation of FE@SUPPY was found in CRC tissue compared to adjacent healthy colon tissue from the same patient. Nevertheless, first in vivo studies using HT-29 xenografts showed insufficient tumor uptake due to (1) poor conservation of target expression in xenografts and (2) unfavorable pharmacokinetics of FE@SUPPY in mice. We therefore conclude that HT-29 xenografts are not adequate to visualize hA3ARs using FE@SUPPY.

Near infrared photoimmunotherapy targeting bladder cancer with a canine anti-epidermal growth factor receptor (EGFR) antibody - Nagaya, Tadanobu; Okuyama, Shuhei; Ogata, Fusa; Maruoka, Yasuhiro; Knapp, Deborah W.; Karagiannis, Sophia N.; Fazekas-Singer, Judit; Choyke, Peter L.; LeBlanc, Amy K.; Jensen-Jarolim, Erika; Kobayashi, Hisataka (Oncotarget)
Anti-epidermal growth factor receptor (EGFR) antibody therapy is used in EGFR expressing cancers including lung, colon, head and neck, and bladder cancers, however results have been modest. Near infrared photoimmunotherapy (NIR-PIT) is a highly selective tumor treatment that employs an antibody-photo-absorber conjugate which is activated by NIR light. NIR-PIT is in clinical trials in patients with recurrent head and neck cancers using cetuximab-IR700 as the conjugate. However, its use has otherwise been restricted to mouse models. This is an effort to explore larger animal models with NIR-PIT. We describe the use of a recombinant canine anti-EGFR monoclonal antibody (mAb), can225IgG, conjugated to the photo-absorber, IR700DX, in three EGFR expressing canine transitional cell carcinoma (TCC) cell lines as a prelude to possible canine clinical studies. Can225-IR700 conjugate showed specific binding and cell-specific killing after NIR-PIT on EGFR expressing cells in vitro. In the in vivo study, can225-IR700 conjugate demonstrated accumulation of the fluorescent conjugate with high tumor-to-background ratio. Tumor-bearing mice were separated into 4 groups: (1) no treatment; (2) 100 μg of can225-IR700 i.v. only; (3) NIR light exposure only; (4) 100 μg of can225-IR700 i.v., NIR light exposure. Tumor growth was significantly inhibited by NIR-PIT treatment compared with the other groups (p < 0.001), and significantly prolonged survival was achieved (p < 0.001 vs. other groups) in the treatment groups. In conclusion, NIR-PIT with can225-IR700 is a promising treatment for canine EGFR-expressing cancers, including invasive transitional cell carcinoma in pet dogs, that could provide a pathway to translation to humans.

Canine macrophages can like human macrophages be in vitro activated toward the M2a subtype relevant in allergy - Herrmann, Ina; Gotovina, Jelena; Fazekas-Singer, Judit; Fischer, Michael B.; Hufnagl, Karin; Bianchini, Rodolfo; Jensen-Jarolim, Erika (Developmental & Comparative Immunology)
The M2a subtype of macrophages plays an important role in human immunoglobulin E (IgE-mediated allergies) and other Th2 type immune reactions. In contrast, very little is known about these cells in the dog. Here we describe an in vitro method to activate canine histiocytic DH82 cells and primary canine monocyte-derived macrophages (MDMs) toward the M2a macrophages using human cytokines. For a side-by-side comparison, we compared the canine cells to human MDMs, and the human monocytic cell line U937 activated towards M1 and M2a cells on the cellular and molecular level. In analogy to activated human M2a cells, canine M2a, differentiated from both DH82 and MDMs, showed an increase in CD206 surface receptor expression compared to M1. Interestingly, canine M2a, but not M1 derived from MDM, upregulated the high-affinity IgE receptor (FcεRI). Transcription levels of M2a-associated genes (IL10, CCL22, TGFβ, CD163) showed a diverse pattern between the human and dog species, whereas M1 genes (IDO1, CXCL11, IL6, TNF-α) were similarly upregulated in canine and human M1 cells (cell lines and MDMs). We suggest that our novel in vitro method will be suitable in comparative allergology studies focussing on macrophages.

Genome rearrangements and selection in multi-chromosome bacteria Burkholderia spp. - Bochkareva, Olga; Moroz, Elena V.; Davydov, Iakov I.; Gelfand, Mikhail S. (BMC Genomics)
Background: The genus Burkholderia consists of species that occupy remarkably diverse ecological niches. Its best known members are important pathogens, B. mallei and B. pseudomallei, which cause glanders and melioidosis, respectively. Burkholderia genomes are unusual due to their multichromosomal organization, generally comprised of 2-3 chromosomes. Results: We performed integrated genomic analysis of 127 Burkholderia strains. The pan-genome is open with the saturation to be reached between 86,000 and 88,000 genes. The reconstructed rearrangements indicate a strong avoidance of intra-replichore inversions that is likely caused by selection against the transfer of large groups of genes between the leading and the lagging strands. Translocated genes also tend to retain their position in the leading or the lagging strand, and this selection is stronger for large syntenies. Integrated reconstruction of chromosome rearrangements in the context of strains phylogeny reveals parallel rearrangements that may indicate inversion-based phase variation and integration of new genomic islands. In particular, we detected parallel inversions in the second chromosomes of B. pseudomallei with breakpoints formed by genes encoding membrane components of multidrug resistance complex, that may be linked to a phase variation mechanism. Two genomic islands, spreading horizontally between chromosomes, were detected in the B. cepacia group. Conclusions: This study demonstrates the power of integrated analysis of pan-genomes, chromosome rearrangements, and selection regimes. Non-random inversion patterns indicate selective pressure, inversions are particularly frequent in a recent pathogen B. mallei, and, together with periods of positive selection at other branches, may indicate adaptation to new niches. One such adaptation could be a possible phase variation mechanism in B. pseudomallei.

Genome rearrangements and phylogeny reconstruction in Yersinia pestis - Bochkareva, Olga; Dranenko, Natalia O.; Ocheredko, Elena S.; Kanevsky, German M.; Lozinsky, Yaroslav N.; Khalaycheva, Vera A.; Artamonova, Irena I.; Gelfand, Mikhail S. (PeerJ)
Genome rearrangements have played an important role in the evolution of Yersinia pestis from its progenitor Yersinia pseudotuberculosis. Traditional phylogenetic trees for Y. pestis based on sequence comparison have short internal branches and low bootstrap supports as only a small number of nucleotide substitutions have occurred. On the other hand, even a small number of genome rearrangements may resolve topological ambiguities in a phylogenetic tree. We reconstructed phylogenetic trees based on genome rearrangements using several popular approaches such as Maximum likelihood for Gene Order and the Bayesian model of genome rearrangements by inversions. We also reconciled phylogenetic trees for each of the three CRISPR loci to obtain an integrated scenario of the CRISPR cassette evolution. Analysis of contradictions between the obtained evolutionary trees yielded numerous parallel inversions and gain/loss events. Our data indicate that an integrated analysis of sequence-based and inversion-based trees enhances the resolution of phylogenetic reconstruction. In contrast, reconstructions of strain relationships based on solely CRISPR loci may not be reliable, as the history is obscured by large deletions, obliterating the order of spacer gains. Similarly, numerous parallel gene losses preclude reconstruction of phylogeny based on gene content.

Bidirectional regulation of COX-2 expression between cancer cells and macrophages - Carvalho, Maria Isabel; Bianchini, Rodolfo; Fazekas-Singer, Judit; Herrmann, Ina; Flickinger, Irene; Thalhammer, Johann G.; Pires, Isabel; Jensen-Jarolim, Erika; Queiroga, Felisbina L. (Anticancer Research)
Background/Aim: Our aim was to investigate the crosstalk between tumor and immune cells (M2 macrophages) and its effects on cyclo-oxygenase-2 (COX2) regulation in canine mammary tumors (CMT). Materials and Methods: Sh1b CMT cells and human BT474 mammary or HT29 colon cancer cells were co-cultured with canine peripheral blood mononuclear cells (PBMCs) or with macrophage-like differentiated THP1 monocytes (dTHP1). Intracellular COX2 expression by PBMCs, dTHP1 and cancer cells was evaluated by flow cytometry. Results: Co-culturing of Sh1b and canine PBMCs induced COX2 overexpression in CMT cells. In turn, COX2 expression by PBMCs, mostly CD68+ macrophages, was attenuated by co-culture with Sh1b (p=0.0001). In accordance, co-culture with dTHP1 prompted intracellular production of COX2 in both Sh1b CMT cells and HT29 human colon cancer cells and reduced production of COX2 in BT474 human mammary cancer cells. The intracellular COX2 expression from dTHP1 decreased when treated with conditioned medium from cultured Sh1b and HT29 cancer cells. Conclusion: Bidirectional COX2 regulation between cancer and monocytes/macrophages might shape a tolerogenic tumor microenvironment in CMT.

Channels: Horizontal scaling and confidentiality on permissioned blockchains - Androulaki, Elli; Cachin, Christian; De Caro, Angelo; Kokoris Kogias, Eleftherios (Computer Security)
Sharding, or partitioning the system’s state so that different subsets of participants handle it, is a proven approach to building distributed systems whose total capacity scales horizontally with the number of participants. Many distributed ledgers have adopted this approach to increase their performance, however, they focus on the permissionless setting that assumes the existence of a strong adversary. In this paper, we deploy channels for permissioned blockchains. Our first contribution is to adapt sharding on asset-management applications for the permissioned setting, while preserving liveness and safety even on transactions spanning across-channels. Our second contribution is to leverage channels as a confidentiality boundary, enabling different organizations and consortia to preserve their privacy within their channels and still be part of a bigger collaborative ecosystem. To make our system concrete we map it on top of Hyperledger Fabric.

OmniLedger: A secure, scale-out, decentralized ledger via sharding - Kokoris Kogias, Eleftherios; Jovanovic, Philipp; Gasser, Linus; Gailly, Nicolas; Syta, Ewa; Ford, Bryan (2018 IEEE Symposium on Security and Privacy)
Designing a secure permissionless distributed ledger (blockchain) that performs on par with centralized payment processors, such as Visa, is a challenging task. Most existing distributed ledgers are unable to scale-out, i.e., to grow their totalprocessing capacity with the number of validators; and those that do, compromise security or decentralization. We present OmniLedger, a novel scale-out distributed ledger that preserves longterm security under permissionless operation. It ensures security and correctness by using a bias-resistant public-randomness protocol for choosing large, statistically representative shards that process transactions, and by introducing an efficient crossshard commit protocol that atomically handles transactions affecting multiple shards. OmniLedger also optimizes performance via parallel intra-shard transaction processing, ledger pruning via collectively-signed state blocks, and low-latency “trust-butverify” validation for low-value transactions. An evaluation ofour experimental prototype shows that OmniLedger’s throughput scales linearly in the number of active validators, supporting Visa-level workloads and beyond, while confirming typical transactions in under two seconds.

How detergent impacts membrane proteins: Atomic-level views of mitochondrial carriers in dodecylphosphocholine - Kurauskas, Vilius; Hessel, Audrey; Ma, Peixiang; Lunetti, Paola; Weinhäupl, Katharina; Imbert, Lionel; Brutscher, Bernhard; King, Martin S.; Sounier, Rémy; Dolce, Vincenza; Kunji, Edmund R. S.; Capobianco, Loredana; et al. (The Journal of Physical Chemistry Letters)
Characterizing the structure of membrane proteins (MPs) generally requires extraction from their native environment, most commonly with detergents. Yet, the physicochemical properties of detergent micelles and lipid bilayers differ markedly and could alter the structural organization of MPs, albeit without general rules. Dodecylphosphocholine (DPC) is the most widely used detergent for MP structure determination by NMR, but the physiological relevance of several prominent structures has been questioned, though indirectly, by other biophysical techniques, e.g., functional/thermostability assay (TSA) and molecular dynamics (MD) simulations. Here, we resolve unambiguously this controversy by probing the functional relevance of three different mitochondrial carriers (MCs) in DPC at the atomic level, using an exhaustive set of solution-NMR experiments, complemented by functional/TSA and MD data. Our results provide atomic-level insight into the structure, substrate interaction and dynamics of the detergent–membrane protein complexes and demonstrates cogently that, while high-resolution NMR signals can be obtained for MCs in DPC, they systematically correspond to nonfunctional states.
Keywords: General Materials Science

The antibiotic cyclomarin blocks arginine-phosphate–induced millisecond dynamics in the N-terminal domain of ClpC1 from Mycobacterium tuberculosis - Weinhäupl, Katharina; Brennich, Martha; Kazmaier, Uli; Lelievre, Joel; Ballell, Lluis; Goldberg, Alfred; Schanda, Paul; Fraga, Hugo (Journal of Biological Chemistry)
Mycobacterium tuberculosis can remain dormant in the host, an ability that explains the failure of many current tuberculosis treatments. Recently, the natural products cyclomarin, ecumicin, and lassomycin have been shown to efficiently kill Mycobacterium tuberculosis persisters. Their target is the N-terminal domain of the hexameric AAA+ ATPase ClpC1, which recognizes, unfolds, and translocates protein substrates, such as proteins containing phosphorylated arginine residues, to the ClpP1P2 protease for degradation. Surprisingly, these antibiotics do not inhibit ClpC1 ATPase activity, and how they cause cell death is still unclear. Here, using NMR and small-angle X-ray scattering, we demonstrate that arginine-phosphate binding to the ClpC1 N-terminal domain induces millisecond dynamics. We show that these dynamics are caused by conformational changes and do not result from unfolding or oligomerization of this domain. Cyclomarin binding to this domain specifically blocked these N-terminal dynamics. On the basis of these results, we propose a mechanism of action involving cyclomarin-induced restriction of ClpC1 dynamics, which modulates the chaperone enzymatic activity leading eventually to cell death.
Keywords: Cell Biology; Biochemistry; Molecular Biology

Perturbations of native membrane protein structure in alkyl phosphocholine detergents: A critical assessment of NMR and biophysical studies - Chipot, Christophe; Dehez, François; Schnell, Jason R.; Zitzmann, Nicole; Pebay-Peyroula, Eva; Catoire, Laurent J.; Miroux, Bruno; Kunji, Edmund R. S.; Veglia, Gianluigi; Cross, Timothy A.; Schanda, Paul (Chemical Reviews)
Membrane proteins perform a host of vital cellular functions. Deciphering the molecular mechanisms whereby they fulfill these functions requires detailed biophysical and structural investigations. Detergents have proven pivotal to extract the protein from its native surroundings. Yet, they provide a milieu that departs significantly from that of the biological membrane, to the extent that the structure, the dynamics, and the interactions of membrane proteins in detergents may considerably vary, as compared to the native environment. Understanding the impact of detergents on membrane proteins is, therefore, crucial to assess the biological relevance of results obtained in detergents. Here, we review the strengths and weaknesses of alkyl phosphocholines (or foscholines), the most widely used detergent in solution-NMR studies of membrane proteins. While this class of detergents is often successful for membrane protein solubilization, a growing list of examples points to destabilizing and denaturing properties, in particular for α-helical membrane proteins. Our comprehensive analysis stresses the importance of stringent controls when working with this class of detergents and when analyzing the structure and dynamics of membrane proteins in alkyl phosphocholine detergents.
Keywords: General Chemistry

Microsecond motions probed by near-rotary-resonance R1ρ 15N MAS NMR experiments: The model case of protein overall-rocking in crystals - Krushelnitsky, Alexey; Gauto, Diego; Rodriguez Camargo, Diana C.; Schanda, Paul; Saalwächter, Kay (Journal of Biomolecular NMR)
Solid-state near-rotary-resonance measurements of the spin–lattice relaxation rate in the rotating frame (R1ρ) is a powerful NMR technique for studying molecular dynamics in the microsecond time scale. The small difference between the spin-lock (SL) and magic-angle-spinning (MAS) frequencies allows sampling very slow motions, at the same time it brings up some methodological challenges. In this work, several issues affecting correct measurements and analysis of 15N R1ρ data are considered in detail. Among them are signal amplitude as a function of the difference between SL and MAS frequencies, “dead time” in the initial part of the relaxation decay caused by transient spin-dynamic oscillations, measurements under HORROR condition and proper treatment of the multi-exponential relaxation decays. The multiple 15N R1ρ measurements at different SL fields and temperatures have been conducted in 1D mode (i.e. without site-specific resolution) for a set of four different microcrystalline protein samples (GB1, SH3, MPD-ubiquitin and cubic-PEG-ubiquitin) to study the overall protein rocking in a crystal. While the amplitude of this motion varies very significantly, its correlation time for all four sample is practically the same, 30–50 μs. The amplitude of the rocking motion correlates with the packing density of a protein crystal. It has been suggested that the rocking motion is not diffusive but likely a jump-like dynamic process.

Solid state NMR studies of intact lipopolysaccharide endotoxin - Laguri, Cedric; Silipo, Alba; Martorana, Alessandra M.; Schanda, Paul; Marchetti, Roberta; Polissi, Alessandra; Molinaro, Antonio; Simorre, Jean-Pierre (ACS Chemical Biology)
Lipopolysaccharides (LPS) are complex glycolipids forming the outside layer of Gram-negative bacteria. Their hydrophobic and heterogeneous nature greatly hampers their structural study in an environment similar to the bacterial surface. We have studied LPS purified from E. coli and pathogenic P. aeruginosa with long O-antigen polysaccharides assembled in solution as vesicles or elongated micelles. Solid-state NMR with magic-angle spinning permitted the identification of NMR signals arising from regions with different flexibilities in the LPS, from the lipid components to the O-antigen polysaccharides. Atomic scale data on the LPS enabled the study of the interaction of gentamicin antibiotic bound to P. aeruginosa LPS, for which we could confirm that a specific oligosaccharide is involved in the antibiotic binding. The possibility to study LPS alone and bound to a ligand when it is assembled in membrane-like structures opens great prospects for the investigation of proteins and antibiotics that specifically target such an important molecule at the surface of Gram-negative bacteria.
Keywords: Molecular Medicine; Biochemistry; General Medicine

Heterogeneous progenitor cell behaviors underlie the assembly of neocortical cytoarchitecture - Llorca, Alfredo; Ciceri, Gabriele; Beattie, Robert J; Wong, Fong K.; Diana, Giovanni; Serafeimidou, Eleni; Fernández-Otero, Marian; Streicher, Carmen; Arnold, Sebastian J.; Meyer, Martin; Hippenmeyer, Simon; Maravall, Miguel; et al. (bioRxiv)
The cerebral cortex contains multiple hierarchically organized areas with distinctive cytoarchitectonical patterns, but the cellular mechanisms underlying the emergence of this diversity remain unclear. Here, we have quantitatively investigated the neuronal output of individual progenitor cells in the ventricular zone of the developing mouse neocortex using a combination of methods that together circumvent the biases and limitations of individual approaches. We found that individual cortical progenitor cells show a high degree of stochasticity and generate pyramidal cell lineages that adopt a wide range of laminar configurations. Mathematical modelling these lineage data suggests that a small number of progenitor cell populations, each generating pyramidal cells following different stochastic developmental programs, suffice to generate the heterogenous complement of pyramidal cell lineages that collectively build the complex cytoarchitecture of the neocortex.

Computing average response time - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan (Principles of Modeling)
Responsiveness—the requirement that every request to a system be eventually handled—is one of the fundamental liveness properties of a reactive system. Average response time is a quantitative measure for the responsiveness requirement used commonly in performance evaluation. We show how average response time can be computed on state-transition graphs, on Markov chains, and on game graphs. In all three cases, we give polynomial-time algorithms.

Targeted assembly and synchronization of self-spinning microgears - Aubret, Antoine; Youssef, Mena; Sacanna, Stefano; Palacci, Jérémie A (Nature Physics)
Self-assembly is the autonomous organization of components into patterns or structures: an essential ingredient of biology and a desired route to complex organization1. At equilibrium, the structure is encoded through specific interactions2,3,4,5,6,7,8, at an unfavourable entropic cost for the system. An alternative approach, widely used by nature, uses energy input to bypass the entropy bottleneck and develop features otherwise impossible at equilibrium9. Dissipative building blocks that inject energy locally were made available by recent advances in colloidal science10,11 but have not been used to control self-assembly. Here we show the targeted formation of self-powered microgears from active particles and their autonomous synchronization into dynamical superstructures. We use a photoactive component that consumes fuel, haematite, to devise phototactic microswimmers that form self-spinning microgears following spatiotemporal light patterns. The gears are coupled via their chemical clouds by diffusiophoresis12 and constitute the elementary bricks of synchronized superstructures, which autonomously regulate their dynamics. The results are quantitatively rationalized on the basis of a stochastic description of diffusio-phoretic oscillators dynamically coupled by chemical gradients. Our findings harness non-equilibrium phoretic phenomena to program interactions and direct self-assembly with fidelity and specificity. It lays the groundwork for the autonomous construction of dynamical architectures and functional micro-machinery.

Diffraction-unlimited optical imaging for synaptic physiology - Danzl, Johann G (Opera Medica et Physiologica)

Timed network games with clocks - Avni, Guy; Guha, Shibashis; Kupferman, Orna
Network games are widely used as a model for selfish resource-allocation problems. In the classicalmodel, each player selects a path connecting her source and target vertices. The cost of traversingan edge depends on theload; namely, number of players that traverse it. Thus, it abstracts the factthat different users may use a resource at different times and for different durations, which playsan important role in determining the costs of the users in reality. For example, when transmittingpackets in a communication network, routing traffic in a road network, or processing a task in aproduction system, actual sharing and congestion of resources crucially depends on time.In [13], we introducedtimed network games, which add a time component to network games.Each vertexvin the network is associated with a cost function, mapping the load onvto theprice that a player pays for staying invfor one time unit with this load. Each edge in thenetwork is guarded by the time intervals in which it can be traversed, which forces the players tospend time in the vertices. In this work we significantly extend the way time can be referred toin timed network games. In the model we study, the network is equipped withclocks, and, as intimed automata, edges are guarded by constraints on the values of the clocks, and their traversalmay involve a reset of some clocks. We argue that the stronger model captures many realisticnetworks. The addition of clocks breaks the techniques we developed in [13] and we developnew techniques in order to show that positive results on classic network games carry over to thestronger timed setting.

Theoretical prediction of the homogeneous ice nucleation rate: Disentangling thermodynamics and kinetics - Cheng, Bingqing; Dellago, Christoph; Ceriotti, Michele (Physical Chemistry Chemical Physics)
Estimating the homogeneous ice nucleation rate from undercooled liquid water is crucial for understanding many important physical phenomena and technological applications, and challenging for both experiments and theory. From a theoretical point of view, difficulties arise due to the long time scales required, as well as the numerous nucleation pathways involved to form ice nuclei with different stacking disorders. We computed the homogeneous ice nucleation rate at a physically relevant undercooling for a single-site water model, taking into account the diffuse nature of ice–water interfaces, stacking disorders in ice nuclei, and the addition rate of particles to the critical nucleus. We disentangled and investigated the relative importance of all the terms, including interfacial free energy, entropic contributions and the kinetic prefactor, that contribute to the overall nucleation rate. Breaking down the problem into pieces not only provides physical insights into ice nucleation, but also sheds light on the long-standing discrepancy between different theoretical predictions, as well as between theoretical and experimental determinations of the nucleation rate. Moreover, we pinpoint the main shortcomings and suggest strategies to systematically improve the existing simulation methods.

Computing the absolute Gibbs free energy in atomistic simulations: Applications to defects in solids - Cheng, Bingqing; Ceriotti, Michele (Physical Review B)
The Gibbs free energy is the fundamental thermodynamic potential underlying the relative stability of different states of matter under constant-pressure conditions. However, computing this quantity from atomic-scale simulations is far from trivial, so the potential energy of a system is often used as a proxy. In this paper, we use a combination of thermodynamic integration methods to accurately evaluate the Gibbs free energies associated with defects in crystals, including the vacancy formation energy in bcc iron, and the stacking fault energy in fcc nickel, iron, and cobalt. We quantify the importance of entropic and anharmonic effects in determining the free energies of defects at high temperatures, and show that the potential energy approximation as well as the harmonic approximation may produce inaccurate or even qualitatively wrong results. Our calculations manifest the necessity to employ accurate free energy methods such as thermodynamic integration to estimate the stability of crystallographic defects at high temperatures.

Is the sky the limit? On the expansion threshold of a species’ range - Polechova, Jitka (PLoS Biology)
More than 100 years after Grigg’s influential analysis of species’ borders, the causes of limits to species’ ranges still represent a puzzle that has never been understood with clarity. The topic has become especially important recently as many scientists have become interested in the potential for species’ ranges to shift in response to climate change—and yet nearly all of those studies fail to recognise or incorporate evolutionary genetics in a way that relates to theoretical developments. I show that range margins can be understood based on just two measurable parameters: (i) the fitness cost of dispersal—a measure of environmental heterogeneity—and (ii) the strength of genetic drift, which reduces genetic diversity. Together, these two parameters define an ‘expansion threshold’: adaptation fails when genetic drift reduces genetic diversity below that required for adaptation to a heterogeneous environment. When the key parameters drop below this expansion threshold locally, a sharp range margin forms. When they drop below this threshold throughout the species’ range, adaptation collapses everywhere, resulting in either extinction or formation of a fragmented metapopulation. Because the effects of dispersal differ fundamentally with dimension, the second parameter—the strength of genetic drift—is qualitatively different compared to a linear habitat. In two-dimensional habitats, genetic drift becomes effectively independent of selection. It decreases with ‘neighbourhood size’—the number of individuals accessible by dispersal within one generation. Moreover, in contrast to earlier predictions, which neglected evolution of genetic variance and/or stochasticity in two dimensions, dispersal into small marginal populations aids adaptation. This is because the reduction of both genetic and demographic stochasticity has a stronger effect than the cost of dispersal through increased maladaptation. The expansion threshold thus provides a novel, theoretically justified, and testable prediction for formation of the range margin and collapse of the species’ range.

Global instability in the restricted planar elliptic three body problem - Delshams, Amadeu; Kaloshin, Vadim; de la Rosa, Abraham; Seara, Tere M. (Communications in Mathematical Physics)
The restricted planar elliptic three body problem (RPETBP) describes the motion of a massless particle (a comet or an asteroid) under the gravitational field of two massive bodies (the primaries, say the Sun and Jupiter) revolving around their center of mass on elliptic orbits with some positive eccentricity. The aim of this paper is to show the existence of orbits whose angular momentum performs arbitrary excursions in a large region. In particular, there exist diffusive orbits, that is, with a large variation of angular momentum. The leading idea of the proof consists in analyzing parabolic motions of the comet. By a well-known result of McGehee, the union of future (resp. past) parabolic orbits is an analytic manifold P+ (resp. P−). In a properly chosen coordinate system these manifolds are stable (resp. unstable) manifolds of a manifold at infinity P∞, which we call the manifold at parabolic infinity. On P∞ it is possible to define two scattering maps, which contain the map structure of the homoclinic trajectories to it, i.e. orbits parabolic both in the future and the past. Since the inner dynamics inside P∞ is trivial, two different scattering maps are used. The combination of these two scattering maps permits the design of the desired diffusive pseudo-orbits. Using shadowing techniques and these pseudo orbits we show the existence of true trajectories of the RPETBP whose angular momentum varies in any predetermined fashion.
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Nearly circular domains which are integrable close to the boundary are ellipses - Huang, Guan; Kaloshin, Vadim; Sorrentino, Alfonso (Geometric and Functional Analysis)
The Birkhoff conjecture says that the boundary of a strictly convex integrable billiard table is necessarily an ellipse. In this article, we consider a stronger notion of integrability, namely integrability close to the boundary, and prove a local version of this conjecture: a small perturbation of an ellipse of small eccentricity which preserves integrability near the boundary, is itself an ellipse. This extends the result in Avila et al. (Ann Math 184:527–558, ADK16), where integrability was assumed on a larger set. In particular, it shows that (local) integrability near the boundary implies global integrability. One of the crucial ideas in the proof consists in analyzing Taylor expansion of the corresponding action-angle coordinates with respect to the eccentricity parameter, deriving and studying higher order conditions for the preservation of integrable rational caustics.
Keywords: Geometry and Topology; Analysis

On the local Birkhoff conjecture for convex billiards - Kaloshin, Vadim; Sorrentino, Alfonso (Annals of Mathematics)
The classical Birkhoff conjecture claims that the boundary of a strictly convex integrable billiard table is necessarily an ellipse (or a circle as a special case). In this article we prove a complete local version of this conjecture: a small integrable perturbation of an ellipse must be an ellipse. This extends and completes the result in Avila-De Simoi-Kaloshin, where nearly circular domains were considered. One of the crucial ideas in the proof is to extend action-angle coordinates for elliptic billiards into complex domains (with respect to the angle), and to thoroughly analyze the nature of their complex singularities. As an application, we are able to prove some spectral rigidity results for elliptic domains.
Keywords: Statistics; Probability and Uncertainty; Statistics and Probability

On the integrability of Birkhoff billiards - Kaloshin, Vadim; Sorrentino, Alfonso (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In this survey, we provide a concise introduction to convex billiards and describe some recent results, obtained by the authors and collaborators, on the classification of integrable billiards, namely the so-called Birkhoff conjecture. This article is part of the theme issue ‘Finite dimensional integrable systems: new trends and methods’.
Keywords: General Engineering; General Physics and Astronomy; General Mathematics

Density of convex billiards with rational caustics - Kaloshin, Vadim; Zhang, Ke (Nonlinearity)
We show that in the space of all convex billiard boundaries, the set of boundaries with rational caustics is dense. More precisely, the set of billiard boundaries with caustics of rotation number 1/q is polynomially sense in the smooth case, and exponentially dense in the analytic case.
Keywords: Mathematical Physics; General Physics and Astronomy; Applied Mathematics; Statistical and Nonlinear Physics

Structural investigation of a chaperonin in action reveals how nucleotide binding regulates the functional cycle - Mas, Guillaume; Guan, Jia-Ying; Crublet, Elodie; Debled, Elisa Colas; Moriscot, Christine; Gans, Pierre; Schoehn, Guy; Macek, Pavel; Schanda, Paul; Boisbouvier, Jerome (Science Advances)
Chaperonins are ubiquitous protein assemblies present in bacteria, eukaryota, and archaea, facilitating the folding of proteins, preventing protein aggregation, and thus participating in maintaining protein homeostasis in the cell. During their functional cycle, they bind unfolded client proteins inside their double ring structure and promote protein folding by closing the ring chamber in an adenosine 5′-triphosphate (ATP)–dependent manner. Although the static structures of fully open and closed forms of chaperonins were solved by x-ray crystallography or electron microscopy, elucidating the mechanisms of such ATP-driven molecular events requires studying the proteins at the structural level under working conditions. We introduce an approach that combines site-specific nuclear magnetic resonance observation of very large proteins, enabled by advanced isotope labeling methods, with an in situ ATP regeneration system. Using this method, we provide functional insight into the 1-MDa large hsp60 chaperonin while processing client proteins and reveal how nucleotide binding, hydrolysis, and release control switching between closed and open states. While the open conformation stabilizes the unfolded state of client proteins, the internalization of the client protein inside the chaperonin cavity speeds up its functional cycle. This approach opens new perspectives to study structures and mechanisms of various ATP-driven biological machineries in the heat of action.

Structural basis of membrane protein chaperoning through the mitochondrial intermembrane space - Weinhäupl, Katharina; Lindau, Caroline; Hessel, Audrey; Wang, Yong; Schütze, Conny; Jores, Tobias; Melchionda, Laura; Schönfisch, Birgit; Kalbacher, Hubert; Bersch, Beate; Rapaport, Doron; Brennich, Martha; et al. (Cell)
The exchange of metabolites between the mitochondrial matrix and the cytosol depends on β-barrel channels in the outer membrane and α-helical carrier proteins in the inner membrane. The essential translocase of the inner membrane (TIM) chaperones escort these proteins through the intermembrane space, but the structural and mechanistic details remain elusive. We have used an integrated structural biology approach to reveal the functional principle of TIM chaperones. Multiple clamp-like binding sites hold the mitochondrial membrane proteins in a translocation-competent elongated form, thus mimicking characteristics of co-translational membrane insertion. The bound preprotein undergoes conformational dynamics within the chaperone binding clefts, pointing to a multitude of dynamic local binding events. Mutations in these binding sites cause cell death or growth defects associated with impairment of carrier and β-barrel protein biogenesis. Our work reveals how a single mitochondrial “transfer-chaperone” system is able to guide α-helical and β-barrel membrane proteins in a “nascent chain-like” conformation through a ribosome-free compartment.
Keywords: General Biochemistry; Genetics and Molecular Biology

Nonisometric domains with the same Marvizi-Melrose invariants - Buhovsky, Lev; Kaloshin, Vadim (Regular and Chaotic Dynamics)
For any strictly convex planar domain Ω ⊂ R2 with a C∞ boundary one can associate an infinite sequence of spectral invariants introduced by Marvizi–Merlose [5]. These invariants can generically be determined using the spectrum of the Dirichlet problem of the Laplace operator. A natural question asks if this collection is sufficient to determine Ω up to isometry. In this paper we give a counterexample, namely, we present two nonisometric domains Ω and Ω¯ with the same collection of Marvizi–Melrose invariants. Moreover, each domain has countably many periodic orbits Snn≥1 (resp. S¯nn⩾1) of period going to infinity such that Sn and S¯n have the same period and perimeter for each n.

Dynamics and interactions of AAC3 in DPC are not functionally relevant - Kurauskas, Vilius; Hessel, Audrey; Dehez, François; Chipot, Christophe; Bersch, Beate; Schanda, Paul (Nature Structural & Molecular Biology)
Keywords: Molecular Biology; Structural Biology

Diffusiophoretic design of self-spinning microgears from colloidal microswimmers - Aubret, Antoine; Palacci, Jérémie A (Soft Matter)
The development of strategies to assemble microscopic machines from dissipative building blocks are essential on the route to novel active materials. We recently demonstrated the hierarchical self-assembly of phoretic microswimmers into self-spinning microgears and their synchronization by diffusiophoretic interactions [Aubret et al., Nat. Phys., 2018]. In this paper, we adopt a pedagogical approach and expose our strategy to control self-assembly and build machines using phoretic phenomena. We notably introduce Highly Inclined Laminated Optical sheets microscopy (HILO) to image and characterize anisotropic and dynamic diffusiophoretic interactions, which cannot be performed by conventional fluorescence microscopy. The dynamics of a (haematite) photocatalytic material immersed in (hydrogen peroxide) fuel under various illumination patterns is first described and quantitatively rationalized by a model of diffusiophoresis, the migration of a colloidal particle in a concentration gradient. It is further exploited to design phototactic microswimmers that direct towards the high intensity of light, as a result of the reorientation of the haematite in a light gradient. We finally show the assembly of self-spinning microgears from colloidal microswimmers and carefully characterize the interactions using HILO techniques. The results are compared with analytical and numerical predictions and agree quantitatively, stressing the important role played by concentration gradients induced by chemical activity to control and design interactions. Because the approach described hereby is generic, this works paves the way for the rational design of machines by controlling phoretic phenomena.
Keywords: General Chemistry; Condensed Matter Physics

Antiferromagnet‐based spintronic functionality by controlling isospin domains in a layered perovskite iridate - Lee, Nara; Ko, Eunjung; Choi, Hwan Young; Hong, Yun Jeong; Nauman, Muhammad; Kang, Woun; Choi, Hyoung Joon; Choi, Young Jai; Jo, Younjung (Advanced Materials)
The novel electronic state of the canted antiferromagnetic (AFM) insulator, strontium iridate (Sr2IrO4) has been well described by the spin-orbit-entangled isospin Jeff = 1/2, but the role of isospin in transport phenomena remains poorly understood. In this study, antiferromagnet-based spintronic functionality is demonstrated by combining unique characteristics of the isospin state in Sr2IrO4. Based on magnetic and transport measurements, large and highly anisotropic magnetoresistance (AMR) is obtained by manipulating the antiferromagnetic isospin domains. First-principles calculations suggest that electrons whose isospin directions are strongly coupled to in-plane net magnetic moment encounter the isospin mismatch when moving across antiferromagnetic domain boundaries, which generates a high resistance state. By rotating a magnetic field that aligns in-plane net moments and removes domain boundaries, the macroscopically-ordered isospins govern dynamic transport through the system, which leads to the extremely angle-sensitive AMR. As with this work that establishes a link between isospins and magnetotransport in strongly spin-orbit-coupled AFM Sr2IrO4, the peculiar AMR effect provides a beneficial foundation for fundamental and applied research on AFM spintronics.
Keywords: Mechanical Engineering; General Materials Science; Mechanics of Materials

Pressure-induced metal–insulator transitions in chalcogenide NiS2-Se - Hussain, Tayyaba; Oh, Myeong-jun; Nauman, Muhammad; Jo, Younjung; Han, Garam; Kim, Changyoung; Kang, Woun (Physica B: Condensed Matter)
We report the temperature-dependent resistivity ρ(T) of chalcogenide NiS2-xSex (x = 0.1) using hydrostatic pressure as a control parameter in the temperature range of 4–300 K. The insulating behavior of ρ(T) survives at low temperatures in the pressure regime below 7.5 kbar, whereas a clear insulator-to-metallic transition is observed above 7.5 kbar. Two types of magnetic transitions, from the paramagnetic (PM) to the antiferromagnetic (AFM) state and from the AFM state to the weak ferromagnetic (WF) state, were evaluated and confirmed by magnetization measurement. According to the temperature–pressure phase diagram, the WF phase survives up to 7.5 kbar, and the transition temperature of the WF transition decreases as the pressure increases, whereas the metal–insulator transition temperature increases up to 9.4 kbar. We analyzed the metallic behavior and proposed Fermi-liquid behavior of NiS1.9Se0.1.

Scaling precipitation extremes with temperature in the Mediterranean: Past climate assessment and projection in anthropogenic scenarios - Drobinski, Philippe; Silva, Nicolas Da; Panthou, Gérémy; Bastin, Sophie; Muller, Caroline J; Ahrens, Bodo; Borga, Marco; Conte, Dario; Fosser, Giorgia; Giorgi, Filippo; Güttler, Ivan; Kotroni, Vassiliki; et al. (Climate Dynamics)
In this study we investigate the scaling of precipitation extremes with temperature in the Mediterranean region by assessing against observations the present day and future regional climate simulations performed in the frame of the HyMeX and MED-CORDEX programs. Over the 1979–2008 period, despite differences in quantitative precipitation simulation across the various models, the change in precipitation extremes with respect to temperature is robust and consistent. The spatial variability of the temperature–precipitation extremes relationship displays a hook shape across the Mediterranean, with negative slope at high temperatures and a slope following Clausius–Clapeyron (CC)-scaling at low temperatures. The temperature at which the slope of the temperature–precipitation extreme relation sharply changes (or temperature break), ranges from about 20 °C in the western Mediterranean to <10 °C in Greece. In addition, this slope is always negative in the arid regions of the Mediterranean. The scaling of the simulated precipitation extremes is insensitive to ocean–atmosphere coupling, while it depends very weakly on the resolution at high temperatures for short precipitation accumulation times. In future climate scenario simulations covering the 2070–2100 period, the temperature break shifts to higher temperatures by a value which is on average the mean regional temperature change due to global warming. The slope of the simulated future temperature–precipitation extremes relationship is close to CC-scaling at temperatures below the temperature break, while at high temperatures, the negative slope is close, but somewhat flatter or steeper, than in the current climate depending on the model. Overall, models predict more intense precipitation extremes in the future. Adjusting the temperature–precipitation extremes relationship in the present climate using the CC law and the temperature shift in the future allows the recovery of the temperature–precipitation extremes relationship in the future climate. This implies negligible regional changes of relative humidity in the future despite the large warming and drying over the Mediterranean. This suggests that the Mediterranean Sea is the primary source of moisture which counteracts the drying and warming impacts on relative humidity in parts of the Mediterranean region.
Keywords: Atmospheric Science

Internal tide dissipation at topography: Triadic resonant instability equatorward and evanescent waves poleward of the critical latitude - Richet, O.; Chomaz, J.-M.; Muller, Caroline J (Journal of Geophysical Research: Oceans)
Several studies have shown the existence of a critical latitude where the dissipation of internal tides is strongly enhanced. Internal tides are internal waves generated by barotropic tidal currents impinging rough topography at the seafloor. Their dissipation and concomitant diapycnal mixing are believed to be important for water masses and the large‐scale ocean circulation. The purpose of this study is to clarify the physical processes at the origin of this strong latitudinal dependence of tidal energy dissipation. We find that different mechanisms are involved equatorward and poleward of the critical latitude. Triadic resonant instabilities are responsible for the dissipation of internal tides equatorward of the critical latitude. In particular, a dominant triad involving the primary internal tide and near‐inertial waves is key. At the critical latitude, the peak of energy dissipation is explained by both increased instability growth rates, and smaller scales of secondary waves thus more prone to break and dissipate their energy. Surprisingly, poleward of the critical latitude, the generation of evanescent waves appears to be crucial. Triadic instabilities have been widely studied, but the transfer of energy to evanescent waves has received comparatively little attention. Our work suggests that the nonlinear transfer of energy from the internal tide to evanescent waves (corresponding to the 2f‐pump mechanism described by Young et al., 2008, https://doi.org/10.1017/S0022112008001742) is an efficient mechanism to dissipate internal tide energy near and poleward of the critical latitude. The theoretical results are confirmed in idealized high‐resolution numerical simulations of a barotropic M2 tide impinging sinusoidal topography in a linearly stratified fluid.

Acceleration of tropical cyclogenesis by self-aggregation feedbacks - Muller, Caroline J; Romps, David M. (Proceedings of the National Academy of Sciences)
Idealized simulations of tropical moist convection have revealed that clouds can spontaneously clump together in a process called self-aggregation. This results in a state where a moist cloudy region with intense deep convection is surrounded by extremely dry subsiding air devoid of deep convection. Because of the idealized settings of the simulations where it was discovered, the relevance of self-aggregation to the real world is still debated. Here, we show that self-aggregation feedbacks play a leading-order role in the spontaneous genesis of tropical cyclones in cloud-resolving simulations. Those feedbacks accelerate the cyclogenesis process by a factor of 2, and the feedbacks contributing to the cyclone formation show qualitative and quantitative agreement with the self-aggregation process. Once the cyclone is formed, wind-induced surface heat exchange (WISHE) effects dominate, although we find that self-aggregation feedbacks have a small but nonnegligible contribution to the maintenance of the mature cyclone. Our results suggest that self-aggregation, and the framework developed for its study, can help shed more light into the physical processes leading to cyclogenesis and cyclone intensification. In particular, our results point out the importance of the longwave radiative cooling outside the cyclone.
Keywords: Multidisciplinary

FACT complex is required for DNA demethylation at heterochromatin during reproduction in Arabidopsis - Frost, Jennifer M.; Kim, M. Yvonne; Park, Guen Tae; Hsieh, Ping-Hung; Nakamura, Miyuki; Lin, Samuel J. H.; Yoo, Hyunjin; Choi, Jaemyung; Ikeda, Yoko; Kinoshita, Tetsu; Choi, Yeonhee; Zilberman, Daniel; et al. (Proceedings of the National Academy of Sciences)
The DEMETER (DME) DNA glycosylase catalyzes genome-wide DNA demethylation and is required for endosperm genomic imprinting and embryo viability. Targets of DME-mediated DNA demethylation reside in small, euchromatic, AT-rich transposons and at the boundaries of large transposons, but how DME interacts with these diverse chromatin states is unknown. The STRUCTURE SPECIFIC RECOGNITION PROTEIN 1 (SSRP1) subunit of the chromatin remodeler FACT (facilitates chromatin transactions), was previously shown to be involved in the DME-dependent regulation of genomic imprinting in Arabidopsis endosperm. Therefore, to investigate the interaction between DME and chromatin, we focused on the activity of the two FACT subunits, SSRP1 and SUPPRESSOR of TY16 (SPT16), during reproduction in Arabidopsis. We found that FACT colocalizes with nuclear DME in vivo, and that DME has two classes of target sites, the first being euchromatic and accessible to DME, but the second, representing over half of DME targets, requiring the action of FACT for DME-mediated DNA demethylation genome-wide. Our results show that the FACT-dependent DME targets are GC-rich heterochromatin domains with high nucleosome occupancy enriched with H3K9me2 and H3K27me1. Further, we demonstrate that heterochromatin-associated linker histone H1 specifically mediates the requirement for FACT at a subset of DME-target loci. Overall, our results demonstrate that FACT is required for DME targeting by facilitating its access to heterochromatin.
Keywords: Multidisciplinary

Collisional charging of individual submillimeter particles: Using ultrasonic levitation to initiate and track charge transfer - Lee, Victor; James, Nicole; Waitukaitis, Scott R; Jaeger, Heinrich (Physical Review Materials)
Electrostatic charging of insulating fine particles can be responsible for numerous phenomena ranging from lightning in volcanic plumes to dust explosions. However, even basic aspects of how fine particles become charged are still unclear. Studying particle charging is challenging because it usually involves the complexities associated with many-particle collisions. To address these issues, we introduce a method based on acoustic levitation, which makes it possible to initiate sequences of repeated collisions of a single submillimeter particle with a flat plate, and to precisely measure the particle charge in situ after each collision. We show that collisional charge transfer between insulators is dependent on the hydrophobicity of the contacting surfaces. We use glass, which we modify by attaching nonpolar molecules to the particle, the plate, or both. We find that hydrophilic surfaces develop significant positive charges after contacting hydrophobic surfaces. Moreover, we demonstrate that charging between a hydrophilic and a hydrophobic surface is suppressed in an acidic environment and enhanced in a basic one. Application of an electric field during each collision is found to modify the charge transfer, again depending on surface hydrophobicity. We discuss these results within the context of contact charging due to ion transfer, and we show that they lend strong support to OH− ions as the charge carriers.

The random k‐matching‐free process - Krivelevich, Michael; Kwan, Matthew Alan; Loh, Po‐Shen; Sudakov, Benny (Random Structures and Algorithms)
Let P be a graph property which is preserved by removal of edges, and consider the random graph process that starts with the empty n-vertex graph and then adds edges one-by-one, each chosen uniformly at random subject to the constraint that P is not violated. These types of random processes have been the subject of extensive research over the last 20 years, having striking applications in extremal combinatorics, and leading to the discovery of important probabilistic tools. In this paper we consider the k-matching-free process, where P is the property of not containing a matching of size k. We are able to analyse the behaviour of this process for a wide range of values of k; in particular we prove that if k=o(n) or if n−2k=o(n−−√/logn) then this process is likely to terminate in a k-matching-free graph with the maximum possible number of edges, as characterised by Erdős and Gallai. We also show that these bounds on k are essentially best possible, and we make a first step towards understanding the behaviour of the process in the intermediate regime.

Counting Hamilton cycles in sparse random directed graphs - Ferber, Asaf; Kwan, Matthew Alan; Sudakov, Benny (Random Structures and Algorithms)
Let D(n,p) be the random directed graph on n vertices where each of the n(n-1) possible arcs is present independently with probability p. A celebrated result of Frieze shows that if p≥(logn+ω(1))/n then D(n,p) typically has a directed Hamilton cycle, and this is best possible. In this paper, we obtain a strengthening of this result, showing that under the same condition, the number of directed Hamilton cycles in D(n,p) is typically n!(p(1+o(1)))n. We also prove a hitting-time version of this statement, showing that in the random directed graph process, as soon as every vertex has in-/out-degrees at least 1, there are typically n!(logn/n(1+o(1)))n directed Hamilton cycles.

Intercalates and discrepancy in random Latin squares - Kwan, Matthew Alan; Sudakov, Benny (Random Structures and Algorithms)
An intercalate in a Latin square is a 2×2 Latin subsquare. Let N be the number of intercalates in a uniformly random n×n Latin square. We prove that asymptotically almost surely N≥(1−o(1))n2/4, and that EN≤(1+o(1))n2/2 (therefore asymptotically almost surely N≤fn2 for any f→∞). This significantly improves the previous best lower and upper bounds. We also give an upper tail bound for the number of intercalates in two fixed rows of a random Latin square. In addition, we discuss a problem of Linial and Luria on low-discrepancy Latin squares.

Non-trivially intersecting multi-part families - Kwan, Matthew Alan; Sudakov, Benny; Vieira, Pedro (Journal of Combinatorial Theory Series A)
We say a family of sets is intersecting if any two of its sets intersect, and we say it is trivially intersecting if there is an element which appears in every set of the family. In this paper we study the maximum size of a non-trivially intersecting family in a natural “multi-part” setting. Here the ground set is divided into parts, and one considers families of sets whose intersection with each part is of a prescribed size. Our work is motivated by classical results in the single-part setting due to Erdős, Ko and Rado, and Hilton and Milner, and by a theorem of Frankl concerning intersecting families in this multi-part setting. In the case where the part sizes are sufficiently large we determine the maximum size of a non-trivially intersecting multi-part family, disproving a conjecture of Alon and Katona.

Hydrogen diffusion and trapping in α-iron: The role of quantum and anharmonic fluctuations - Cheng, Bingqing; Paxton, Anthony T.; Ceriotti, Michele (Physical Review Letters)
We investigate the thermodynamics and kinetics of a hydrogen interstitial in magnetic α-iron, taking account of the quantum fluctuations of the proton as well as the anharmonicities of lattice vibrations and hydrogen hopping. We show that the diffusivity of hydrogen in the lattice of bcc iron deviates strongly from an Arrhenius behavior at and below room temperature. We compare a quantum transition state theory to explicit ring polymer molecular dynamics in the calculation of diffusivity. We then address the trapping of hydrogen by a vacancy as a prototype lattice defect. By a sequence of steps in a thought experiment, each involving a thermodynamic integration, we are able to separate out the binding free energy of a proton to a defect into harmonic and anharmonic, and classical and quantum contributions. We find that about 30% of a typical binding free energy of hydrogen to a lattice defect in iron is accounted for by finite temperature effects, and about half of these arise from quantum proton fluctuations. This has huge implications for the comparison between thermal desorption and permeation experiments and standard electronic structure theory. The implications are even greater for the interpretation of muon spin resonance experiments.

Communication: Computing the Tolman length for solid-liquid interfaces - Cheng, Bingqing; Ceriotti, Michele (The Journal of Chemical Physics)
The curvature dependence of interfacial free energy, which is crucial in quantitatively predicting nucleation kinetics and the stability of bubbles and droplets, is quantified by the Tolman length δ. For solid-liquid interfaces, however, δ has never been computed directly due to various theoretical and practical challenges. Here we perform a direct evaluation of the Tolman length from atomistic simulations of a solid-liquid planar interface in out-of-equilibrium conditions, by first computing the surface tension from the amplitude of thermal capillary fluctuations of a localized version of the Gibbs dividing surface and by then calculating how much the surface energy changes when it is defined relative to the equimolar dividing surface. We computed δ for a model potential, and found a good agreement with the values indirectly inferred from nucleation simulations. The agreement not only validates our approach but also suggests that the nucleation free energy of the system can be perfectly described using classical nucleation theory if the Tolman length is taken into account.

Interannual variability in glacier contribution to runoff from a high‐elevation Andean catchment: Understanding the role of debris cover in glacier hydrology - Burger, Flavia; Ayala, Alvaro; Farias, David; Shaw, Thomas E.; MacDonell, Shelley; Brock, Ben; McPhee, James; Pellicciotti, Francesca (Hydrological Processes)
We present a field-data rich modelling analysis to reconstruct the climatic forcing, glacier response, and runoff generation from a high-elevation catchment in central Chile over the period 2000–2015 to provide insights into the differing contributions of debris-covered and debris-free glaciers under current and future changing climatic conditions. Model simulations with the physically based glacio-hydrological model TOPKAPI-ETH reveal a period of neutral or slightly positive mass balance between 2000 and 2010, followed by a transition to increasingly large annual mass losses, associated with a recent mega drought. Mass losses commence earlier, and are more severe, for a heavily debris-covered glacier, most likely due to its strong dependence on snow avalanche accumulation, which has declined in recent years. Catchment runoff shows a marked decreasing trend over the study period, but with high interannual variability directly linked to winter snow accumulation, and high contribution from ice melt in dry periods and drought conditions. The study demonstrates the importance of incorporating local-scale processes such as snow avalanche accumulation and spatially variable debris thickness, in understanding the responses of different glacier types to climate change. We highlight the increased dependency of runoff from high Andean catchments on the diminishing resource of glacier ice during dry years.
Keywords: Water Science and Technology

Snow depth structure, fractal behavior, and interannual consistency over Haut Glacier d'Arolla, Switzerland - Clemenzi, I.; Pellicciotti, Francesca; Burlando, P. (Water Resources Research)
Snow depth patterns over glaciers are controlled by precipitation, snow redistribution due to wind and avalanches, and the exchange of energy with the atmosphere that determines snow ablation. While many studies have advanced the understanding of ablation processes, less is known about winter snow patterns and their variability over glaciers. We analyze snow depth on Haut Glacier d'Arolla, Switzerland, in the two winter seasons 2006–2007 and 2010–2011 to (1) understand whether snow depth over an alpine glacier at the end of the accumulation season exhibits a behavior similar to the one observed on single slopes and vegetated areas; and (2) investigate the snow pattern consistency over the two accumulation seasons. We perform this analysis on a data set of high-resolution lidar-derived snow depth using variograms and fractal parameters. Our first main result is that snow depth patterns on the glacier exhibit a multiscale behavior, with a scale break around 20 m after which the fractal dimension increases, indicating more autocorrelated structure before the scale break than after. Second, this behavior is consistent over the two years, with fractal parameters and their spatial variability almost constant in the two seasons. We also show that snow depth patterns exhibit a distinct behavior in the glacier tongue and the upper catchment, with longer correlation distances on the tongue in the direction of the main winds, suggesting spatial distinctions that are likely induced by different processes and that should be taken into account when extrapolating snow depth from limited samples.
Keywords: Water Science and Technology

Surface pond energy absorption across four Himalayan Glaciers accounts for 1/8 of total catchment ice loss - Miles, Evan S.; Willis, Ian; Buri, Pascal; Steiner, Jakob F.; Arnold, Neil S.; Pellicciotti, Francesca (Geophysical Research Letters)
Glaciers in the high mountains of Asia provide an important water resource for millions of people. Many of these glaciers are partially covered by rocky debris, which protects the ice from solar radiation and warm air. However, studies have found that the surface of these debris-covered glaciers is actually lowering as fast as glaciers without debris. Water ponded on the surface of the glaciers may be partially responsible, as water can absorb atmospheric energy very efficiently. However, the overall effect of these ponds has not been thoroughly assessed yet. We study a valley in Nepal for which we have extensive weather measurements, and we use a numerical model to calculate the energy absorbed by ponds on the surface of the glaciers over 6 months. As we have not observed each individual pond thoroughly, we run the model 5,000 times with different setups. We find that ponds are extremely important for glacier melt and absorb energy 14 times as quickly as the debris-covered ice. Although the ponds account for 1% of the glacier area covered by rocks, and only 0.3% of the total glacier area, they absorb enough energy to account for one eighth of the whole valley's ice loss.
Keywords: General Earth and Planetary Sciences; Geophysics

Aspect controls the survival of ice cliffs on debris-covered glaciers - Buri, Pascal; Pellicciotti, Francesca (PNAS)
Supraglacial ice cliffs exist on debris-covered glaciers worldwide, but despite their importance as melt hot spots, their life cycle is little understood. Early field observations had advanced a hypothesis of survival of north-facing and disappearance of south-facing cliffs, which is central for predicting the contribution of cliffs to total glacier mass losses. Their role as windows of energy transfer suggests they may explain the anomalously high mass losses of debris-covered glaciers in High Mountain Asia (HMA) despite the insulating debris, currently at the center of a debated controversy. We use a 3D model of cliff evolution coupled to very high-resolution topographic data to demonstrate that ice cliffs facing south (in the Northern Hemisphere) disappear within a few months due to enhanced solar radiation receipts and that aspect is the key control on cliffs evolution. We reproduce continuous flattening of south-facing cliffs, a result of their vertical gradient of incoming solar radiation and sky view factor. Our results establish that only north-facing cliffs are recurrent features and thus stable contributors to the melting of debris-covered glaciers. Satellite observations and mass balance modeling confirms that few south-facing cliffs of small size exist on the glaciers of Langtang, and their contribution to the glacier volume losses is very small (∼1%). This has major implications for the mass balance of HMA debris-covered glaciers as it provides the basis for new parameterizations of cliff evolution and distribution to constrain volume losses in a region where glaciers are highly relevant as water sources for millions of people.

Automated detection of ice cliffs within supraglacial debris cover - Herreid, Sam; Pellicciotti, Francesca (The Cryosphere)
Ice cliffs within a supraglacial debris cover have been identified as a source for high ablation relative to the surrounding debris-covered area. Due to their small relative size and steep orientation, ice cliffs are difficult to detect using nadir-looking space borne sensors. The method presented here uses surface slopes calculated from digital elevation model (DEM) data to map ice cliff geometry and produce an ice cliff probability map. Surface slope thresholds, which can be sensitive to geographic location and/or data quality, are selected automatically. The method also attempts to include area at the (often narrowing) ends of ice cliffs which could otherwise be neglected due to signal saturation in surface slope data. The method was calibrated in the eastern Alaska Range, Alaska, USA, against a control ice cliff dataset derived from high-resolution visible and thermal data. Using the same input parameter set that performed best in Alaska, the method was tested against ice cliffs manually mapped in the Khumbu Himal, Nepal. Our results suggest the method can accommodate different glaciological settings and different DEM data sources without a data intensive (high-resolution, multi-data source) recalibration.
Keywords: Earth-Surface Processes; Water Science and Technology

Supported two-dimensional materials under ion irradiation: The substrate governs defect production - Kretschmer, Silvan; Maslov, Mikhail; Ghaderzadeh, Sadegh; Ghorbani-Asl, Mahdi; Hlawacek, Gregor; Krasheninnikov, Arkady V. (ACS Applied Materials & Interfaces)
Focused ion beams perfectly suit for patterning two-dimensional (2D) materials, but the optimization of irradiation parameters requires full microscopic understanding of defect production mechanisms. In contrast to freestanding 2D systems, the details of damage creation in supported 2D materials are not fully understood, whereas the majority of experiments have been carried out for 2D targets deposited on substrates. Here, we suggest a universal and computationally efficient scheme to model the irradiation of supported 2D materials, which combines analytical potential molecular dynamics with Monte Carlo simulations and makes it possible to independently assess the contributions to the damage from backscattered ions and atoms sputtered from the substrate. Using the scheme, we study the defect production in graphene and MoS2 sheets, which are the two most important and wide-spread 2D materials, deposited on a SiO2 substrate. For helium and neon ions with a wide range of initial ion energies including those used in a commercial helium ion microscope (HIM), we demonstrate that depending on the ion energy and mass, the defect production in 2D systems can be dominated by backscattered ions and sputtered substrate atoms rather than by the direct ion impacts and that the amount of damage in 2D materials heavily depends on whether a substrate is present or not. We also study the factors which limit the spatial resolution of the patterning process. Our results, which agree well with the available experimental data, provide not only insights into defect production but also quantitative information, which can be used for the minimization of damage during imaging in HIM or optimization of the patterning process.
Keywords: General Materials Science

Reversible photoswitching of encapsulated azobenzenes in water - Samanta, Dipak; Gemen, Julius; Chu, Zonglin; Diskin-Posner, Yael; Shimon, Linda J. W.; Klajn, Rafal (Proceedings of the National Academy of Sciences)
Efficient molecular switching in confined spaces is critical for the successful development of artificial molecular machines. However, molecular switching events often entail large structural changes and therefore require conformational freedom, which is typically limited under confinement conditions. Here, we investigated the behavior of azobenzene—the key building block of light-controlled molecular machines—in a confined environment that is flexible and can adapt its shape to that of the bound guest. To this end, we encapsulated several structurally diverse azobenzenes within the cavity of a flexible, water-soluble coordination cage, and investigated their light-responsive behavior. Using UV/Vis absorption spectroscopy and a combination of NMR methods, we showed that each of the encapsulated azobenzenes exhibited distinct switching properties. An azobenzene forming a 1:1 host–guest inclusion complex could be efficiently photoisomerized in a reversible fashion. In contrast, successful switching in inclusion complexes incorporating two azobenzene guests was dependent on the availability of free cages in the system, and it involved reversible trafficking of azobenzene between the cages. In the absence of extra cages, photoswitching was either suppressed or it involved expulsion of azobenzene from the cage and consequently its precipitation from the solution. This finding was utilized to develop an information storage medium in which messages could be written and erased in a reversible fashion using light.
Keywords: Multidisciplinary

Reversible chromism of spiropyran in the cavity of a flexible coordination cage - Samanta, Dipak; Galaktionova, Daria; Gemen, Julius; Shimon, Linda J. W.; Diskin-Posner, Yael; Avram, Liat; Král, Petr; Klajn, Rafal (Nature Communications)
Confining molecules to volumes only slightly larger than the molecules themselves can profoundly alter their properties. Molecular switches—entities that can be toggled between two or more forms upon exposure to an external stimulus—often require conformational freedom to isomerize. Therefore, placing these switches in confined spaces can render them non-operational. To preserve the switchability of these species under confinement, we work with a water-soluble coordination cage that is flexible enough to adapt its shape to the conformation of the encapsulated guest. We show that owing to its flexibility, the cage is not only capable of accommodating—and solubilizing in water—several light-responsive spiropyran-based molecular switches, but, more importantly, it also provides an environment suitable for the efficient, reversible photoisomerization of the bound guests. Our findings pave the way towards studying various molecular switching processes in confined environments.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

“Precipitation on nanoparticles”: Attractive intermolecular interactions stabilize specific ligand ratios on the surfaces of nanoparticles - Chu, Zonglin; Han, Yanxiao; Král, Petr; Klajn, Rafal (Angewandte Chemie International Edition)
Confining organic molecules to the surfaces of inorganic nanoparticles can induce intermolecular interactions between them, which can affect the composition of the mixed self-assembled monolayers obtained by co-adsorption from solution of two different molecules. Two thiolated ligands (a dialkylviologen and a zwitterionic sulfobetaine) that can interact with each other electrostatically were coadsorbed onto gold nanoparticles. The nanoparticles favor a narrow range of ratios of these two molecules that is largely independent of the molar ratio in solution. Changing the solution molar ratio of the two ligands by a factor of 5 000 affects the on-nanoparticle ratio of these ligands by only threefold. This behavior is reminiscent of the formation of insoluble inorganic salts (such as AgCl), which similarly compensate positive and negative charges upon crystallizing. Our results pave the way towards developing well-defined hybrid organic–inorganic nanostructures.
Keywords: General Chemistry; Catalysis

Dissipative self-assembly driven by the consumption of chemical fuels - De, Soumen; Klajn, Rafal (Advanced Materials)
Dissipative self-assembly leads to structures and materials that exist away from equilibrium by continuously exchanging energy and materials with the external environment. Although this mode of self-assembly is ubiquitous in nature, where it gives rise to functions such as signal processing, motility, self-healing, self-replication, and ultimately life, examples of dissipative self-assembly processes in man-made systems are few and far between. Herein, recent progress in developing diverse synthetic dissipative self-assembly systems is discussed. The systems reported thus far can be categorized into three classes, in which: i) the fuel chemically modifies the building blocks, thus triggering their self-assembly, ii) the fuel acts as a template interacting with the building blocks noncovalently, and iii) transient states are induced by the addition of two mutually exclusive stimuli. These early studies give rise to materials that would be difficult to obtain otherwise, including hydrogels with programmable lifetimes, vesicular nanoreactors, and membranes exhibiting transient conductivity.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Integrating macromolecules with molecular switches - Bléger, David; Klajn, Rafal (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Spectral models for binary products: Unifying subdwarfs and Wolf-Rayet stars as a sequence of stripped-envelope stars - Götberg, Ylva Louise Linsdotter; de Mink, S. E.; Groh, J. H.; Kupfer, T.; Crowther, P. A.; Zapartas, E.; Renzo, M. (Astronomy & Astrophysics)
Stars stripped of their hydrogen-rich envelope through interaction with a binary companion are generally not considered when accounting for ionizing radiation from stellar populations, despite the expectation that stripped stars emit hard ionizing radiation, form frequently, and live 10–100 times longer than single massive stars. We compute the first grid of evolutionary and spectral models specially made for stars stripped in binaries for a range of progenitor masses (2–20 M⊙) and metallicities ranging from solar to values representative for pop II stars. For stripped stars with masses in the range 0.3–7 M⊙, we find consistently high effective temperatures (20 000–100 000 K, increasing with mass), small radii (0.2–1 R⊙), and high bolometric luminosities, comparable to that of their progenitor before stripping. The spectra show a continuous sequence that naturally bridges subdwarf-type stars at the low-mass end and Wolf-Rayet-like spectra at the high-mass end. For intermediate masses we find hybrid spectral classes showing a mixture of absorption and emission lines. These appear for stars with mass-loss rates of 10−8−10−6 M⊙ yr−1, which have semi-transparent atmospheres. At low metallicity, substantial hydrogen-rich layers are left at the surface and we predict spectra that resemble O-type stars instead. We obtain spectra undistinguishable from subdwarfs for stripped stars with masses up to 1.7 M⊙, which questions whether the widely adopted canonical value of 0.47 M⊙ is uniformly valid. Only a handful of stripped stars of intermediate mass have currently been identified observationally. Increasing this sample will provide necessary tests for the physics of interaction, internal mixing, and stellar winds. We use our model spectra to investigate the feasibility to detect stripped stars next to an optically bright companion and recommend systematic searches for their UV excess and possible emission lines, most notably HeII λ4686 in the optical and HeII λ1640 in the UV. Our models are publicly available for further investigations or inclusion in spectral synthesis simulations.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Clues about the scarcity of stripped-envelope stars from the evolutionary state of the sdO+Be binary system φ Persei - Schootemeijer, A.; Götberg, Ylva Louise Linsdotter; de Mink, S. E.; Gies, D.; Zapartas, E. (Astronomy & Astrophysics)
Stripped-envelope stars form in binary systems after losing mass through Roche-lobe overflow. They bear astrophysical significance as sources of UV and ionizing radiation in older stellar populations and, if sufficiently massive, as stripped supernova progenitors. Binary evolutionary models predict that they are common, but only a handful of subdwarfs with B-type companions are known. The question is whether a large population of such systems has evaded detection as a result of biases, or whether the model predictions are wrong. We reanalyze the well-studied post-interaction binary φ Persei. Recently, new data have improved the orbital solution of the system, which contains an ~1.2M⊙ stripped-envelope star and a rapidly rotating ~9.6M⊙ Be star. We compare with an extensive grid of evolutionary models using a Bayesian approach and constrain the initial masses of the progenitor to 7.2 ± 0.4M⊙ for the stripped star and 3.8 ± 0.4M⊙ for the Be star. The system must have evolved through near-conservative mass transfer. These findings are consistent with earlier studies. The age we obtain, 57 ± 9 Myr, is in excellent agreement with the age of the α Persei cluster. We note that neither star was initially massive enough to produce a core-collapse supernova, but mass exchange pushed the Be star above the mass threshold. We find that the subdwarf is overluminous for its mass by almost an order of magnitude, compared to the expectations for a helium core burning star. We can only reconcile this if the subdwarf resides in a late phase of helium shell burning, which lasts only 2–3% of the total lifetime as a subdwarf. Assuming continuous star formation implies that up to ~50 less evolved, dimmer subdwarfs exist for each system similar to φ Persei, but have evaded detection so far. Our findings can be interpreted as a strong indication that a substantial population of stripped-envelope stars indeed exists, but has so far evaded detection because of observational biases and lack of large-scale systematic searches.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Extreme isolation of WN3/O3 stars and implications for their evolutionary origin as the elusive stripped binaries - Smith, Nathan; Götberg, Ylva Louise Linsdotter; de Mink, Selma E (Monthly Notices of the Royal Astronomical Society)
Recent surveys of the Magellanic Clouds have revealed a subtype of Wolf–Rayet (WR) star with peculiar properties. WN3/O3 spectra exhibit both WR-like emission and O3 V-like absorption – but at lower luminosity than O3 V or WN stars. We examine the projected spatial distribution of WN3/O3 stars in the Large Magellanic Cloud as compared to O-type stars. Surprisingly, WN3/O3 stars are among the most isolated of all classes of massive stars; they have a distribution similar to red supergiants dominated by initial masses of 10–15 M⊙, and are far more dispersed than classical WR stars or luminous blue variables. Their lack of association with clusters of O-type stars suggests strongly that WN3/O3 stars are not the descendants of single massive stars (30 M⊙ or above). Instead, they are likely products of interacting binaries at lower initial mass (10–18 M⊙). Comparison with binary models suggests a probable origin with primaries in this mass range that were stripped of their H envelopes through non-conservative mass transfer by a low-mass secondary. We show that model spectra and positions on the Hertzsprung–Russell diagram for binary-stripped stars are consistent with WN3/O3 stars. Monitoring radial velocities with high-resolution spectra can test for low-mass companions or runaway velocities. With lower initial mass and environments that avoid very massive stars, the WN3/O3 stars fit expectations for progenitors of Type Ib and possibly Type Ibn supernovae.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The ℤ2-Genus of Kuratowski minors - Fulek, Radoslav; Kynčl, Jan
A drawing of a graph on a surface is independently even if every pair of nonadjacent edges in the drawing crosses an even number of times. The ℤ2-genus of a graph G is the minimum g such that G has an independently even drawing on the orientable surface of genus g. An unpublished result by Robertson and Seymour implies that for every t, every graph of sufficiently large genus contains as a minor a projective t × t grid or one of the following so-called t-Kuratowski graphs: K3, t, or t copies of K5 or K3,3 sharing at most 2 common vertices. We show that the ℤ2-genus of graphs in these families is unbounded in t; in fact, equal to their genus. Together, this implies that the genus of a graph is bounded from above by a function of its ℤ2-genus, solving a problem posed by Schaefer and Štefankovič, and giving an approximate version of the Hanani-Tutte theorem on orientable surfaces.

Chiral discrimination through bielliptical high-harmonic spectroscopy - Baykusheva, Denitsa Rangelova; Wörner, Hans Jakob (Physical Review X)
Molecular chirality plays an essential role in most biochemical processes. The observation and quantification of chirality-sensitive signals, however, remains extremely challenging, especially on ultrafast timescales and in dilute media. Here, we describe the experimental realization of an all-optical and ultrafast scheme for detecting chiral dynamics in molecules. This technique is based on high-harmonic generation by a combination of two-color counterrotating femtosecond laser pulses with polarization states tunable from linear to circular. We demonstrate two different implementations of chiral-sensitive high-harmonic spectroscopy on an ensemble of randomly oriented methyloxirane molecules in the gas phase. Using two elliptically polarized fields, we observe that the ellipticities maximizing the harmonic signal reach up to 4.4 ± 0.2 % (at 17.6 eV). Using two circularly polarized fields, we observe circular dichroisms ranging up to 13 ± 6 % (28.3–33.1 eV). Our theoretical analysis confirms that the observed chiral response originates from subfemtosecond electron dynamics driven by the magnetic component of the driving laser field. This assignment is supported by the experimental observation of a strong intensity dependence of the chiral effects and its agreement with theory. We moreover report and explain a pronounced variation of the signal strength and dichroism with the driving-field ellipticities and harmonic orders. Finally, we demonstrate the sensitivity of the experimental observables to the shape of the electron hole. This technique for chiral discrimination will yield femtosecond temporal resolution when integrated in a pump-probe scheme and subfemtosecond resolution on chiral charge migration in a self-probing scheme.
Keywords: General Physics and Astronomy

Thrackles: An improved upper bound - Fulek, Radoslav; Pach, János
A thrackle is a graph drawn in the plane so that every pair of its edges meet exactly once: either at a common end vertex or in a proper crossing. We prove that any thrackle of n vertices has at most 1.3984n edges. Quasi-thrackles are defined similarly, except that every pair of edges that do not share a vertex are allowed to cross an odd number of times. It is also shown that the maximum number of edges of a quasi-thrackle on n vertices is 3/2(n-1), and that this bound is best possible for infinitely many values of n.

Data from: Multiple chromosomal rearrangements in a hybrid zone between Littorina saxatilis ecotypes - Faria, Rui; Chaube, Pragya; Morales, Hernán E.; Larsson, Tomas; Lemmon, Alan R.; Lemmon, Emily M.; Rafajlović, Marina; Panova, Marina; Ravinet, Mark; Johannesson, Kerstin; Westram, Anja M; Butlin, Roger K.
Both classical and recent studies suggest that chromosomal inversion polymorphisms are important in adaptation and speciation. However, biases in discovery and reporting of inversions make it difficult to assess their prevalence and biological importance. Here, we use an approach based on linkage disequilibrium among markers genotyped for samples collected across a transect between contrasting habitats to detect chromosomal rearrangements de novo. We report 17 polymorphic rearrangements in a single locality for the coastal marine snail, Littorina saxatilis. Patterns of diversity in the field and of recombination in controlled crosses provide strong evidence that at least the majority of these rearrangements are inversions. Most show clinal changes in frequency between habitats, suggestive of divergent selection, but only one appears to be fixed for different arrangements in the two habitats. Consistent with widespread evidence for balancing selection on inversion polymorphisms, we argue that a combination of heterosis and divergent selection can explain the observed patterns and should be considered in other systems spanning environmental gradients.

Cost analysis of nondeterministic probabilistic programs - Anonymous, 1; Anonymous, 2; Anonymous, 3; Anonymous, 4; Anonymous, 5; Anonymous, 6
We consider the problem of expected cost analysis over nondeterministic probabilistic programs, which aims at automated methods for analyzing the resource-usage of such programs. Previous approaches for this problem could only handle nonnegative bounded costs. However, in many scenarios, such as queuing networks or analysis of cryptocurrency protocols, both positive and negative costs are necessary and the costs are unbounded as well. In this work, we present a sound and efficient approach to obtain polynomial bounds on the expected accumulated cost of nondeterministic probabilistic programs. Our approach can handle (a) general positive and negative costs with bounded updates in variables; and (b) nonnegative costs with general updates to variables. We show that several natural examples which could not be handled by previous approaches are captured in our framework. Moreover, our approach leads to an efficient polynomial-time algorithm, while no previous approach for cost analysis of probabilistic programs could guarantee polynomial runtime. Finally, we show the effectiveness of our approach by presenting experimental results on a variety of programs, motivated by real-world applications, for which we efficiently synthesize tight resource-usage bounds.

Absorption and directed Jónsson terms - Kazda, Alexandr; Kozik, Marcin; McKenzie, Ralph; Moore, Matthew (Don Pigozzi on Abstract Algebraic Logic, Universal Algebra, and Computer Science)
We prove that every congruence distributive variety has directed Jónsson terms, and every congruence modular variety has directed Gumm terms. The directed terms we construct witness every case of absorption witnessed by the original Jónsson or Gumm terms. This result is equivalent to a pair of claims about absorption for admissible preorders in congruence distributive and congruence modular varieties, respectively. For finite algebras, these absorption theorems have already seen significant applications, but until now, it was not clear if the theorems hold for general algebras as well. Our method also yields a novel proof of a result by P. Lipparini about the existence of a chain of terms (which we call Pixley terms) in varieties that are at the same time congruence distributive and k-permutable for some k.

Shellability is NP-complete - Goaoc, Xavier; Paták, Pavel; Patakova, Zuzana; Tancer, Martin; Wagner, Uli
We prove that for every d ≥ 2, deciding if a pure, d-dimensional, simplicial complex is shellable is NP-hard, hence NP-complete. This resolves a question raised, e.g., by Danaraj and Klee in 1978. Our reduction also yields that for every d ≥ 2 and k ≥ 0, deciding if a pure, d-dimensional, simplicial complex is k-decomposable is NP-hard. For d ≥ 3, both problems remain NP-hard when restricted to contractible pure d-dimensional complexes.

On the treewidth of triangulated 3-manifolds - Huszár, Kristóf; Spreer, Jonathan; Wagner, Uli
In graph theory, as well as in 3-manifold topology, there exist several width-type parameters to describe how "simple" or "thin" a given graph or 3-manifold is. These parameters, such as pathwidth or treewidth for graphs, or the concept of thin position for 3-manifolds, play an important role when studying algorithmic problems; in particular, there is a variety of problems in computational 3-manifold topology - some of them known to be computationally hard in general - that become solvable in polynomial time as soon as the dual graph of the input triangulation has bounded treewidth. In view of these algorithmic results, it is natural to ask whether every 3-manifold admits a triangulation of bounded treewidth. We show that this is not the case, i.e., that there exists an infinite family of closed 3-manifolds not admitting triangulations of bounded pathwidth or treewidth (the latter implies the former, but we present two separate proofs). We derive these results from work of Agol and of Scharlemann and Thompson, by exhibiting explicit connections between the topology of a 3-manifold M on the one hand and width-type parameters of the dual graphs of triangulations of M on the other hand, answering a question that had been raised repeatedly by researchers in computational 3-manifold topology. In particular, we show that if a closed, orientable, irreducible, non-Haken 3-manifold M has a triangulation of treewidth (resp. pathwidth) k then the Heegaard genus of M is at most 48(k+1) (resp. 4(3k+1)).